Absorbent articles having highly permeable SAP
The absorbent article addresses the challenges of fluid management and comfort by using high-permeable superabsorbent polymer particles and an upper capture and distribution system without unbound crosslinked cellulose fibers, achieving effective absorption and preventing leakage in air felt-free cores.
Patent Information
- Application Number
- JP2024551661
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-09
- Publication Date
- 2025-04-11
AI Technical Summary
Existing absorbent articles face challenges in achieving good fluid management properties, comfort, and maintaining integrity during use, particularly with air felt-free cores that lack sufficient absorption rates and are prone to product leakage.
The development of an absorbent article with a liquid permeable topsheet, an absorbent core comprising a layer of high-permeable superabsorbent polymer particles, and an upper capture and distribution system substantially free of unbound crosslinked cellulose fibers, which provides a balanced capacity and permeability.
This configuration enables absorbent articles with air felt-free cores to achieve capture rates comparable to those with crosslinked cellulose fibers, while maintaining comfort and preventing leakage, even under high liquid loads.
Smart Images

Figure 2025509146000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to absorbent articles for personal hygiene, such as baby diapers and adult incontinence products. [Background technology]
[0002] Disposable absorbent articles, such as diapers, include an absorbent core disposed between a liquid-permeable topsheet facing the wearer and a liquid-impermeable backsheet facing the garment. The absorbent core typically includes an absorbent material disposed within a core wrap. Urine passes through the topsheet into the absorbent article and is absorbed by the absorbent material.
[0003] Superabsorbent polymers (SAPs) are commonly used as absorbent materials. Surface cross-linking is known to increase the permeability and swelling rate of SAPs, but different performance profiles of SAPs are also known to trade one property for another. Specifically, one of the known trade-offs is between permeability and capacity. Increasing the permeability of SAPs can improve the locally accessible capacity at faster bursts, but this reduces the capacity for slower bursts and higher loads, where capacity is a more important property than permeability.
[0004] The superabsorbent polymer is typically in the form of particles mixed with cellulose fibers (the cores are called "fluff pulp" or "airfelt" cores). Absorbent cores that do not contain cellulose fibers ("airfelt-free" cores) have also been proposed. SAP can be encapsulated, for example, in individual pockets formed between two substrate layers (see, for example, WO 95 / 11654, Tanzer et al.). It has also been proposed to immobilize SAP particles to a nonwoven substrate with a microfiber thermoplastic adhesive network (see, for example, WO 2008 / 155699(A1), Hundorf et al.).
[0005] Most personal absorbent hygiene articles have an acquisition layer directly under the topsheet. The acquisition layer provides rapid acquisition of fluid from the topsheet. In some absorbent articles, a distribution layer is additionally present between the acquisition layer and the absorbent core. The distribution layer distributes fluids across the plane of the absorbent article to maximize the use of absorbent material. The distribution layer may be in direct contact with the absorbent core. Distribution layers made of crosslinked cellulose fibers have been used in combination with airfelt-free cores, see for example US Patent Application Publication No. 2008 / 0312622 (Hundorf). Crosslinked cellulose fibers have a fast acquisition rate, but distribution layers made from these crosslinked cellulose fibers show poor integrity during use because unbonded cellulose fibers can form wet clumps. Such distribution layers may be several times thicker than the dry absorbent core.
[0006] The overall sensory performance of the absorbent article is desirably soft, thin, and flexible. A combination of soft nonwoven layers has recently been proposed as an acquisition and distribution system for airfelt-free core articles (see, for example, US Patent Application Publication No. 2021 / 0106471 (Yuan)). However, the relatively reduced volume and lower permeability of these nonwovens may result in slower acquisition times, which may lead to increased product leakage during use. In particular, airfelt-free absorbent cores may not have sufficient absorption rates to adequately handle large amounts of liquid (as superabsorbent polymer materials typically absorb liquid slower than cellulose fibers, especially when the first gush of liquid wets the article).
[0007] To maintain leakage performance, it is possible to increase the overall amount of SAP in the core, but this leads to higher material costs. More recently, it has been proposed to place a lower acquisition and distribution layer between the absorbent core and the backsheet to improve fluid acquisition properties (see WO 2021 / 118904 (Grenier)). Such a lower acquisition and distribution layer can improve acquisition time, but the performance may still be slower than a diaper with an upper acquisition and distribution system that includes crosslinked cellulose fibers as the distribution layer. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 95 / 11654 [Patent Document 2] International Publication No. 2008 / 155699(A1) [Patent Document 3] US Patent Application Publication No. 2008 / 0312622 [Patent Document 4] U.S. Patent Application Publication No. 2021 / 0106471 [Patent Document 5] International Publication No. 2021 / 118904 Summary of the Invention [Problem to be solved by the invention]
[0009] Thus, there is a need for an absorbent article that addresses the above problems, specifically, one that has good fluid management properties, is comfortable to use, and does not lose its integrity during use. [Means for solving the problem]
[0010] In a first aspect, the present invention is directed to an absorbent article comprising a liquid permeable topsheet, an absorbent core comprising a layer of superabsorbent polymer particles and a core wrap, an upper acquisition and distribution system consisting of a layer disposed between the topsheet and the absorbent core, and a liquid impermeable backsheet. The superabsorbent polymer particles have a urine permeability of at least 45.10 as measured by the Urine Permeability Measurement (UPM) method described herein. -7 (cm 3 s) / g and preferably has a usable capacity of greater than 23 g / g, where the usable capacity is measured as described herein. Preferably, the superabsorbent polymer particles are not mixed with cellulose fibers.
[0011] The upper acquisition and distribution system is defined by all layers between the topsheet and the absorbent core. The upper acquisition and distribution system may include one, two or more layers and is substantially free of unbonded crosslinked cellulosic fibers.
[0012] The present invention allows absorbent articles that do not have crosslinked cellulosic fibers in the upper acquisition-distribution system to have acquisition rates comparable to absorbent articles that have crosslinked cellulosic fibers in the upper ADS (acquisition-distribution system).Surprisingly, it has been found that absorbent articles with airfelt-free cores particularly benefit from the use of highly permeable SAPs, even though this reduces the overall core capacity compared to higher capacity SAPs.
[0013] The SAP used in the present invention provides the right balance between capacity and permeability, especially for airfelt-free cores that include an upper acquisition and distribution system that is substantially free of crosslinked cellulose fibers. The upper acquisition and distribution system may in particular include a spunlace nonwoven, which has been found to be particularly useful in replacing crosslinked cellulose fibers.
[0014] In a further aspect of the invention, the absorbent core may include one or more longitudinally extending channel forming regions formed by bonding together upper and lower sides of the core wrap in material free areas surrounded by absorbent material, the channel forming region(s) forming a three dimensional channel when wetted.
[0015] Thus, the absorbent article may also optionally include a lower acquisition-distribution layer disposed between the absorbent layer and the backsheet. The lower acquisition-distribution layer is preferably disposed between the absorbent core and the backsheet, but may also be disposed within the absorbent core inside the core wrap. [Brief description of the drawings]
[0016] While the specification concludes with claims which particularly set forth and distinctly claim the invention, it is believed that the contents of this specification will be better understood from the following description read in conjunction with the accompanying drawings, in which: [Figure 1] FIG. 1 is a diagram of an exemplary absorbent article in the form of a diaper. [Diagram 2] FIG. 2 is a transverse cross-sectional view of the diaper of FIG. 1. [Figure 3A] FIG. 2 is an alternative transverse cross-sectional view of a diaper with a lower acquisition and distribution layer. [Figure 3B] FIG. 2 is an alternative transverse cross-sectional view of a diaper with a lower acquisition and distribution layer. [Figure 3C] FIG. 2 is an alternative transverse cross-sectional view of a diaper with a lower acquisition and distribution layer. [Figure 4] FIG. 2 is a top view of an exemplary absorbent core with the top layer partially removed. [Diagram 5] FIG. 5 is a longitudinal cross-sectional view of the absorbent core of FIG. [Figure 6] 5 is a transverse cross-sectional view of the absorbent core of FIG. 4. [Figure 7] FIG. 1 is a partial cross-sectional side view of a suitable permeability measurement system for performing a urine permeability measurement test. [Figure 8]FIG. 1 is a cross-sectional side view of a piston / cylinder assembly for use in performing a urine permeability measurement test. [Figure 9] FIG. 8 is a top view of a piston head suitable for use in the piston / cylinder assembly shown in FIG. [Figure 10] FIG. 9 is a cross-sectional side view of the piston / cylinder assembly of FIG. 8 positioned over a fritted disc for the swelling phase. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] definition As used herein, "absorbent article" refers to a personal hygiene device that is placed against or proximal to the wearer's crotch to absorb and contain bodily exudates and absorb and contain various exudates discharged from the body. Absorbent articles include taped and pant diapers (for babies, toddlers, and adults), absorbent inserts (intended to be inserted into an outer cover to form a diaper or pant), feminine care absorbent articles such as sanitary napkins or panty liners, and the like. As used herein, the term "exudates" includes, but is not limited to, urine, blood, vaginal discharge, sweat, and feces. The absorbent articles of the present invention are typically disposable and preferably recyclable.
[0018] As used herein, "diaper" generally refers to an absorbent article worn by infants, toddlers and incontinent adults around the lower torso, encircling the waist and legs of the wearer, and adapted to receive and contain urine and fecal exudates in particular. Diapers are typically proposed as taped diapers or pant diapers. Taped diapers have a fastening system (e.g., as shown in FIG. 1 ) in which the longitudinal edges of the front and rear waist regions are releasably attached to one another when the diaper is applied to the wearer. In contrast, in pant diapers, the longitudinal edges of the waist region are attached to one another to form preformed waist and leg openings. Pant diapers are placed in position on the wearer by inserting the wearer's legs into the leg openings and sliding the pant diaper into position around the wearer's lower torso. The pant may be preformed by any suitable technique, including, but not limited to, joining portions of the absorbent article together using refastenable and / or non-refastenable bonding materials (e.g., stitching, welding, adhesives, adhesive bonding materials, fasteners, etc.) The pant may be preformed anywhere along the circumference of the article (e.g., side fastened, front waist fastened).
[0019] As used herein, the terms "nonwoven," "nonwoven web," and "nonwoven layer" are used interchangeably. A nonwoven is broadly defined as a primarily planar, man-made fiber assembly that is endowed with a designed level of structural integrity by physical and / or chemical means other than weaving, knitting, or papermaking. The fibers can be of natural origin, such as cotton or bamboo fibers, or of man-made origin. The synthetic fibers can be selected from the group consisting of polyolefins (such as polyethylene, polypropylene, or combinations and mixtures thereof), polyethylene terephthalate (PET), co-PET, polylactic acid (PLA), polyhydroxy alkanoid (PHA), or mixtures or combinations thereof. The fibers can be staple fibers (e.g., carded nonwoven webs / layers) or continuous fibers (e.g., spunbond or meltblown nonwoven webs / layers).
[0020] Nonwoven webs / layers can be formed by many processes, such as meltblowing, spunlay, solvent spinning, electrospinning and carding, and the fibers can be consolidated, for example, by hydroentanglement (in spunlaced nonwoven webs / layers), air-through bonding (using hot air blown through the fiber layer in the thickness direction), needle punching, one or more bond patterns and bond impressions created by localized compression and / or application of heat or ultrasonic energy, or combinations thereof. The fibers can alternatively or additionally be consolidated by the use of a binder. The binder can be provided in the form of binder fibers (which are subsequently melted) or in a liquid, such as a styrene butadiene binder. The liquid binder is provided to the fibers (e.g., by spraying, printing or foam application) and then cured to solidify. The basis weight of a nonwoven fabric is typically measured in grams per square meter (g / m 2 )
[0021] The term "spunlace" refers to a nonwoven fabric in which the binding and entanglement of fibers with each other is obtained by multiple water jets under pressure passing through a moving fleece or fabric, such as needles, which causes the fibers to interweave with each other. These spunlaces are essentially defined by their consolidation resulting from hydroentanglement. As used herein, "spunlace" also refers to a nonwoven fabric formed from two or more webs (layers), which are combined with each other by hydroentanglement. The two webs may undergo a bonding process, such as heat and / or pressure bonding, for example by applying a bonding pattern using a patterned calendar roll and an anvil roll, before being combined into one nonwoven fabric by hydroentanglement. However, the two webs are combined with each other only by hydroentanglement.
[0022] "Monocomponent" refers to fibers formed of a single polymeric component or a single blend of polymeric components, as distinguished from bicomponent or multicomponent fibers.
[0023] "Bicomponent" refers to a fiber having a cross-section that includes two separate polymeric components, two separate blends of polymeric components, or one separate polymeric component and a blend of one separate polymeric component. "Bicomponent fiber" is subsumed within the term "multicomponent fiber." Bicomponent fibers can have an overall cross-section that is divided into subsections of two different components in any shape or arrangement, including, for example, concentric core and sheath subsections, eccentric core and sheath subsections, side-by-side subsections, radial subsections, and the like.
[0024] "Multicomponent fibers" include, but are not limited to, "bicomponent fibers." Multicomponent fibers may have an overall cross-section divided into different component subsections of any shape or arrangement, including, for example, concentric core and sheath subsections, eccentric core and sheath subsections, side-by-side subsections, islands-in-the-sea subsections, segmented pie subsections, etc.
[0025] Nonwoven materials can be formed from a variety of fibrous materials (PP, PE, PET, coPET, bicomponent, and mixtures thereof) and in some cases the fibers or nonwovens can be treated to enhance certain fluid handling properties, such as fluid permeability or fluid barrier properties.
[0026] "dtex" as used herein refers to the unit used to indicate the fineness of a filament / fiber. This unit represents the mass of the filament / fiber in grams per 10,000 meters of length.
[0027] "Hydrophilic" describes the surface of a substrate that can be wetted by aqueous fluids (e.g., aqueous body fluids) deposited on these substrates. Hydrophilicity and wettability are typically defined by the contact angle of the fluid and the breakthrough time of the fluid, e.g., through a nonwoven fabric. This is discussed in detail in a publication of the American Chemical Society, edited by Robert F. Gould, entitled "Contact Angle, Wettability and Adhesion", Copyright 1964. The surface of a substrate is said to be wetted by a fluid (i.e., hydrophilic) either when the contact angle between the fluid and the surface is less than 90° or when the fluid tends to spread spontaneously across the surface of the substrate (usually both conditions coexist). Conversely, if the contact angle is greater than 90° and the fluid does not spread spontaneously across the surface of the fiber, the substrate is considered "hydrophobic".
[0028] "Longitudinal" refers to a direction extending substantially perpendicular from a waist edge to an opposing waist edge of the article and generally parallel to the maximum linear dimension of the article (line 80 in FIG. 1). "Transverse" refers to a direction perpendicular to the longitudinal direction (line 90 in FIG. 1).
[0029] "Inner" and "outer" refer to the relative position of an element, or a surface of an element, or a group of elements, respectively. "Inner" means that the element or surface is oriented toward the inside of the article, and "outer" means that the element or surface is oriented toward the outside of the article.
[0030] "Body-facing" and "garment-facing" refer to a surface of an element, or the relative location of a group of elements, respectively. "Body-facing" means that the surface is closer to the wearer during wear than the other surface of the element of the group of elements. "Garment-facing" means that the surface is oriented away from the wearer during wear. The garment-facing surface may face another garment of the wearer (i.e., other than the wearable article), other articles such as bedding, or the atmosphere.
[0031] "Comprise, comprising, and comprises" are open-ended terms, each of which specifies the presence of the subsequently described feature (e.g., component) but does not exclude the presence of other features (e.g., elements, steps, components known in the art or disclosed herein). These terms based on the verb "comprise" encompass the narrower term "consisting essentially of," which excludes any unmentioned element, step, or ingredient that materially affects the manner in which the feature performs its function, and the term "consisting of," which excludes any unspecified element, step, or ingredient.
[0032] Exemplary Diaper Overview 1 is a plan view of an exemplary diaper 20 laid out flat with portions of the diaper structure cut away to more clearly show the diaper structure. This diaper 20 is shown for illustrative purposes only, as the structure of the present invention may be included in a wide variety of diapers or other absorbent articles, such as pant diapers, having preformed side seams. The side seams of the pant article can be cut or otherwise opened if it is desired to arrange the pant in a configuration similar to that of FIG. 1 laid out flat.
[0033] 1-2, the absorbent article comprises a topsheet 24 on its wearer-facing surface, a backsheet 25 on its garment-facing surface, and an absorbent core 28 between the topsheet 24 and the backsheet 25. The absorbent core 28 includes at least one layer 60 of superabsorbent polymer particles ("SAP") and a core wrap. The layer of SAP is disposed between an upper core wrap layer 45 and a lower core wrap layer 46.
[0034] The SAP layer typically has a predetermined contour (perimeter) as considered in the plane formed by the article when laid flat. This contour may be substantially rectangular as shown in FIG. 1, or may be other shapes such as hourglass or dogbone. The absorbent core 28 may further include at least one longitudinally oriented channel forming region 26, which is a substantially SAP-free region defined within the SAP layer. The channel forming region(s) 26 facilitate fluid distribution along the length of the absorbent article. Exemplary absorbent core structures are described in more detail below in connection with FIGS. 4-6.
[0035] The absorbent article of the present invention further comprises an upper acquisition-distribution system. The upper acquisition-distribution system as defined herein consists of all layers between the topsheet and the absorbent core. The upper acquisition-distribution system typically comprises at least an upper acquisition layer 52 immediately below the topsheet, and optionally a distribution layer 54 between the acquisition layer and the absorbent core. The upper acquisition-distribution layer may also consist of a single layer, or three layers, or even more layers.
[0036] The upper acquisition and distribution system of the present invention is preferably composed of one or more nonwoven layers or layers. The acquisition layer 52 can be, for example, a latex-bonded nonwoven acquisition layer, treated with a surfactant. Crosslinked cellulose fibers have been used in the past as distribution layers with airfelt-free absorbent cores, but these cellulose fibers are loose, i.e., unbonded, and therefore do not have the integrity of a nonwoven. One objective of the present invention is to eliminate unbonded crosslinked cellulose fibers without compromising the rate of fluid acquisition and distribution in the article. Thus, the upper acquisition and distribution system does not include such unbonded crosslinked cellulose fibers. By unbonded, it is meant that the fibers do not form a web that can be manipulated without a support layer, such as a nonwoven or airlaid, but rather the unbonded fibers form patches that have only a loose integrity and the fibers can be lightly separated by hand.
[0037] An example of a distribution layer that can be used in the present invention is a spunlace layer, however other materials, particularly nonwoven materials, having fluid acquisition and distribution properties and integrity may be used.
[0038] Suitable spunlace nonwovens include absorbent fibers, stiffening fibers, and elastic fibers, as disclosed, for example, in WO 2020 / 205485 (Peri et al.). Spunlace nonwovens may typically include about 20 percent to about 75 percent absorbent fibers, about 1 percent to about 50 percent stiffening fibers, and about 10 percent to about 50 percent elastic fibers.
[0039] Any suitable absorbent fiber can be used. Some conventional absorbent fibers include cotton, rayon, or regenerated cellulose, or combinations thereof. In one embodiment, the absorbent fiber can include viscose cellulose fiber. The absorbent fiber can include staple long fibers. The staple length of the absorbent fiber can range from about 20 mm to about 100 mm, or from about 30 mm to about 50 mm, or from about 35 mm to about 45 mm. As mentioned above, in addition to the absorbent fiber, the spunlace of the present invention can also include stiffening fibers. Stiffening fibers can be used to help impart structural integrity to the nonwoven. Stiffening fibers can help increase the structural integrity of the nonwoven in the machine direction and cross machine direction, which can facilitate web manipulation during processing of the nonwoven for incorporation into disposable absorbent articles. Any suitable stiffening fiber can be used. Some examples of suitable stiffening fibers include bicomponent fibers, including polyethylene and polyethylene terephthalate components or polyethylene terephthalate and copolyethylene terephthalate components. The components of the bicomponent fiber can be arranged in a core-sheath configuration, a side-by-side configuration, an eccentric core-sheath configuration, a trilobal configuration, etc. In one particular example, the stiffening fiber can include a bicomponent fiber having polyethylene / polyethylene terephthalate components arranged in a concentric core-sheath configuration with the polyethylene being the sheath. As another example, a monocomponent fiber can be used and the monocomponent component material can include polypropylene or polylactic acid (PLA). It is worth noting that these components, such as polypropylene and polylactic acid, can also be used in bicomponent fibers.
[0040] The elastic fibers help the spunlace maintain its permeability and cushioning properties. Suitable fibers that may be utilized include hollow fibers, helical fibers, and / or hollow helical fibers, among others. For example, the elastic fibers can have a linear density of about 4 dtex to about 12 dtex, about 6 dtex to about 11 dtex, or about 8 dtex to about 10 dtex, including these ranges and all values within any range defined by these ranges. In one particular example, the elastic fibers can include hollow helical (HS) polyethylene terephthalate fibers with a linear density of about 10 dtex. In another particular example, the elastic fibers can include circular polyethylene terephthalate fibers with 6.7 dtex.
[0041] As shown in Figure 1, the absorbent article can be conceptually divided into a front waist region 36, a rear waist region 38 opposite the first waist region 36, and a crotch region 37 located between the front waist region 36 and the rear waist region 38. The crotch region, front waist region, and rear waist region are defined herein as each defining one-third of the length of the absorbent article along a longitudinal centerline 80. The longitudinal centerline 80 is an imaginary line that bisects the diaper into left and right halves along its length. The transverse centerline 90 is an imaginary line that is perpendicular to the longitudinal centerline 80 in the plane of the diaper laid flat and runs through the middle of the diaper's length. The perimeter of the diaper 20 is defined by the outer edges of the diaper. The longitudinal edges 13 of the diaper may extend generally parallel to the longitudinal centerline 80 of the diaper 20, and the front waist edge 10 and the back waist edge 12 typically extend generally parallel to the transverse centerline 90 of the diaper 20. However, these article edges need not be straight, but may be curved to better fit the wearer.
[0042] Additionally, the absorbent article may comprise other optional but conventional elements not shown for simplicity, such as rear waist elastic features, front waist elastic features, lotion applied on the body-facing surface of the topsheet, or a urine indicator disposed on the inside of the backsheet that changes color when in contact with urine.
[0043] The topsheet 24, backsheet 25 and absorbent core 28 may be assembled in a variety of known configurations, in particular by gluing, heat embossing, ultrasonic bonding or combinations thereof. Exemplary diaper constructions are outlined in U.S. Patent Nos. 3,860,003, 5,221,274, 5,554,145, 5,569,234, 5,580,411 and 6,004,306.
[0044] The topsheet 24 is the portion of the absorbent article that contacts the wearer's skin. At least a portion of the topsheet, or the entirety of it, is liquid permeable, allowing liquid body exudates to easily penetrate through its thickness. Suitable topsheets can be made from a wide range of materials, such as, for example, porous foams, reticulated foams, perforated plastic films, woven materials, nonwoven materials, woven or nonwoven materials of natural fibers (e.g., wood fibers or cotton fibers), synthetic fibers or filaments (e.g., polypropylene fibers, or bicomponent PE / PP fibers, or mixtures thereof), or combinations of natural and synthetic fibers. The topsheet can have one or more layers. The topsheet can be perforated or nonperforated, can have any suitable three-dimensional features, and / or can have multiple embossments (e.g., bond patterns). Any portion of the topsheet can be coated with a skin care composition, an antimicrobial agent, a surfactant, and / or other beneficial agents. The topsheet can be hydrophilic or hydrophobic, or can have hydrophilic portions or layers and / or hydrophobic portions or layers. If the topsheet is hydrophobic, there will typically be holes present to allow body exudates to pass through the topsheet.
[0045] The backsheet 25 is generally that portion of the absorbent article 20 that constitutes all or a portion of the garment-facing surface of the absorbent article. The backsheet 25 may be at least partially joined to the topsheet 24, the absorbent core 28, or the lower acquisition and distribution layer 56, if present, by any attachment method known to those skilled in the art. The backsheet prevents, or at least inhibits, bodily exudates absorbed and contained in the absorbent core from soiling articles such as bed sheets, undergarments, and / or clothing. The backsheet is typically liquid impermeable, or at least substantially liquid impermeable.
[0046] The backsheet typically comprises a thin impermeable plastic film, such as a thermoplastic film having a thickness of about 0.01 mm to about 0.05 mm. The backsheet material may be breathable, allowing vapors to escape from the absorbent article while still preventing, or at least inhibiting, body exudates from passing through the backsheet. A breathable backsheet has a surface area of 1,000 to 15,000 g / m2, as measured using a PERMATRAN-W Model 101K (Mocon, Inc., Minneapolis, MN) or equivalent in accordance with Nonwovens Standard Procedure NWSP 70.4.R0(15), with the following specifications: experiments are conducted in a controlled laboratory at 23°C ± 2°C and 50% RH ± 2% RH, and the instrument cell is heated to 37.8°C (100°F). 2 / 24h, or 1,000~10,000g / m 2 / 24h, or 1,500~10,000g / m 2 / 24h Water Vapor Transmission Rate (WVTR).
[0047] The backsheet 25 may also include a backsheet outer cover nonwoven (not shown). The backsheet outer cover nonwoven is typically a thin nonwoven material bonded to the outer surface of the backsheet film. The outer cover nonwoven may thus form the garment-facing surface of the backsheet. The backsheet outer cover nonwoven may include bond patterns, openings, and / or three-dimensional features to improve the feel of the backsheet.
[0048] The absorbent article 20 may also include inner barrier leg cuffs 34 and outer leg cuffs 32, as is known in the art. The inner barrier cuffs 34 may extend upwardly from the surface of the article to provide retention of bodily exudates, while the outer cuffs are typically formed in the plane of the chassis of the article as defined by the topsheet and backsheet. These cuffs are preferably elasticized, as is known in the art, using, for example, elastic yarns 33, 35 as depicted in the figures.
[0049] Additionally, the absorbent article may further comprise a fastening system, such as an adhesive fastener system or a hook and loop fastener member, which may comprise a tape tab 42 disposed on the back ear 40, such as an adhesive tape tab, or a tape tab with a hook element, that cooperates with a landing zone 44 (e.g., a nonwoven web that provides a loop in a hook and loop fastener system). Taped diapers typically comprise back ears 40 and front ears 43, which are typically not present in pant-type absorbent articles that have preformed side seams.
[0050] Alternatively, the front and / or back ears may be separate components attached to the absorbent article, or instead may be continuous with portions of the topsheet and / or backsheet such that they form all or part of the front ear 43 and / or back ear 40. Combinations of the above are also possible, whereby the front ear 43 and / or back ear 40 are formed by portions of the topsheet and / or backsheet, while additional material is applied to form the entire front ear 43 and / or back ear 40. The front and / or back ear may be elastic or inelastic. Also, the front ear 40 may be applied as a separate component attached to the absorbent article, while the back ear (or portions thereof) may be continuous with portions of the backsheet and / or topsheet, or vice versa.
[0051] Absorbent core 28 The absorbent core comprises at least one layer of superabsorbent polymer particles (SAP). SAP, as known in the art, are water-insoluble, water-swellable polymers capable of absorbing large amounts of fluid. The term "superabsorbent polymer" as used herein refers to absorbent materials, typically cross-linked polymeric materials, capable of absorbing at least 10 times their weight in 0.9% saline, as measured using the Centrifuge Retention Capacity (CRC) test, as set forth in EDANA method NWSP241.0.R2(19). SAPs may specifically have CRC values greater than 20 g / g, or greater than 24 g / g, or between 20 and 50 g / g, or between 20 and 40 g / g, or between 24 and 35 g / g. SAPs used in the present invention are described in more detail in the following sections.
[0052] The SAPs are typically secured within a core wrap that includes an upper core wrap layer and a lower core wrap layer so that the absorbent core can be easily integrated with the remainder of the chassis of the absorbent article on a processing line.
[0053] While in the prior art superabsorbent polymer particles are often mixed with cellulose fibers (airfelt cores), the absorbent core of the present invention includes at least one SAP layer in which SAP particles are not mixed with cellulose fibers. Thus, the resulting layer of absorbent material may have a reduced thickness in the dry state compared to conventional airfelt-based absorbent cores. The reduced thickness helps to improve the fit and comfort of the absorbent article to the wearer. The absorbent core of the present invention may preferably be completely free of unbound cellulose fibers (however, some cellulose fibers may be present in bound form in nonwoven or tissue layers such as spunlace layers). Many absorbent core designs may be used in the present invention. For example, if the core wrap includes a tissue paper layer, some cellulose fibers may be present within the core wrap. Thus, although not preferred, it is also possible for the absorbent core to have a thickness of at least 45.10 mm. -7 (cm 3 It is not excluded that the layer may include a separate layer of cellulose fibers or a separate airfelt / SAP blend layer, so long as it is different from the layer of SAP having a urine permeability of 0.05 s / g.
[0054] Various absorbent core designs including a layer of SAP without cellulosic fibers have been proposed in the past, see for example U.S. Pat. No. 5,599,335 (Goldman), European Patent No. 1,447,066 (Busam), WO 95 / 11652 (Tanzer), U.S. Patent Application Publication No. 2008 / 0312622 (A1) (Hundorf), WO 2012 / 052172 (Van Malderen). In particular, the SAP printing techniques disclosed in U.S. Patent Application Publication Nos. 2006 / 024433 (Blessing), 2008 / 0312617 and 2010 / 0051166 (A1) (both to Hundorf et al.) may be used.
[0055] A layer of SAP may be deposited on at least one layer of the absorbent core that typically functions as a substrate, such as a lower core wrap layer or an upper core wrap layer. In a SAP printing process, such as that described in U.S. Patent Application Publication No. 2008 / 312,622(A1) (Hundorf), a continuous layer of SAP is obtained by depositing SAP on each of the core wrap layers in a pattern having absorbent material land areas separated by bond areas that are free of absorbent material. The absorbent material land areas of the first layer substantially correspond to the bond areas that are free of absorbent material of the second layer, and vice versa, such that when the two discontinuous layers are combined, a continuous layer of SAP is obtained.
[0056] The absorbent core may include one or more adhesives, particularly auxiliary adhesives applied between the inner surface of one or both of the core wrap layers and the SAP layer, to adhere and secure the SAP within the core wrap. Also, as described in the Hundorf reference above, a microfibrous thermoplastic adhesive net may be used in the airfelt-free core to secure the SAP. These adhesives are not shown in the figures for simplicity.
[0057] Other core structures may also be used in the present disclosure, including, for example, a high loft nonwoven substrate, such as a carded nonwoven layer, having a porous structure in which SAP particles are deposited.
[0058] The layer of SAP may be deposited as a continuous layer within the core wrap, or it may be present discontinuously, for example as individual pockets or stripes of absorbent material encapsulated within the core wrap and separated from one another by bonded areas that are free of material.
[0059] The basis weight (amount of deposition per surface unit) of the superabsorbent material can be varied to create a contoured distribution of superabsorbent material longitudinally, but also transversely across the core, or in both directions, to provide more absorbency, particularly in the crotch region of the article.
[0060] The core wrap is formed by one or two substrate layers that sandwich and at least partially immobilize the SAP particles so that the absorbent core maintains its integrity. The upper core wrap layer 45 and the lower core wrap layer 46 are also referred to in the art as the core cover and dusting layers, respectively. These core wrap layers are typically low basis weight nonwovens (typically less than 20 gsm, especially 8 gsm to 14 gsm), and may in particular be SMS nonwovens (spunbond-meltblown-spunbond laminates), as known in the art. The upper and lower core wrap layers may be any material capable of containing and providing support for the absorbent material.
[0061] The core wrap layers can be made from the same or different materials, i.e., two nonwoven webs having the same or different properties, for example, in a c-wrap configuration. To simplify the construction and include a single longitudinal seal, the core wrap may also be made from a single continuous nonwoven web that is wrapped around the layer of absorbent material, in which case the upper and lower core wrap layers are made from the same web material.
[0062] 4-6 show an exemplary absorbent body comprising an upper core wrap layer 45 oriented toward the topsheet, a lower core wrap layer 46 oriented toward the backsheet, and a layer of SAP 60 between the two core wrap layers. The absorbent core shown has two longitudinal edges 284, 286 formed by the core wraps, a front transverse edge 280, and a rear transverse edge 282.
[0063] The core wrap layers are preferably bonded longitudinally by one or more longitudinal core wrap bond(s) 29 to prevent the absorbent material from escaping laterally from the absorbent core. The core wrap layers may also optionally be bonded transversely at the front and back sides of the absorbent core by one or more transverse core wrap bonds 84. The core wrap layers may be bonded at least longitudinally face-to-face as shown in FIG. 2, although other bonding configurations are possible, particularly a C-wrap configuration in which one of the upper or lower core wrap layers is larger than the other, such that flaps may be folded around the absorbent material and attached to the other core wrap layer, as illustrated in FIG. 6. The transversely extending portions of the upper core wrap layer 45 may surround the entire longitudinal edges 284, 286 of the core and may be bonded outwardly to the lower wrap layer 46 such that these flap portions are positioned on the garment-facing surface of the absorbent core. Alternatively, the flap portions at the longitudinal edges of the lower core wrap layer and the flap portions adjacent thereto can be folded over the lateral edges of the core so that the flap portions are positioned on the body-facing surface of the absorbent core.
[0064] The upper core wrap layer 45 and the lower core wrap layer 46 typically at least partially or completely surround the layer of SAP 60 to provide dry and wet immobilization of the absorbent material. In addition, the SAP layer may be at least partially secured onto the upper core wrap layer 45 and / or onto the lower core wrap layer 46 (and / or onto the lower acquisition-distribution layer 56, if present in the core wrap) by a hot melt adhesive applied between the substrate layer and the SAP and / or by a thermoplastic fiber network applied onto the layer of SAP.
[0065] The absorbent core 28 optionally includes at least one channel-forming region 26 that is substantially free of absorbent material (although in some cases some superabsorbent particles may be accidentally deposited during core fabrication). The channel-forming region preferably does not extend to any of the sides of the absorbent layer and is therefore completely surrounded by absorbent material. The channel-forming region is typically elongated in the longitudinal direction and has a longitudinal length that is 20% to 80%, or 20% to 70%, or 30% to 60% of the longitudinal length of the layer 60 of SAP (longitudinal length means the length measured projected onto the longitudinal axis). The absorbent core may typically include a pair of channel-forming regions symmetrically disposed on each side of the longitudinal axis 80, which may be straight, curved, or a combination thereof. Such a pair of channel-forming regions may be disconnected, as shown in FIG. 4. The channel-forming regions may also be connected, for example, at one or both of their ends to form a U-shape or an O-shape. Examples of channel-forming regions are disclosed in further detail in WO 2012170778(A1) and WO 2012170781 (Kreuzer et al.).
[0066] The upper core wrap layer 45 and the lower core wrap layer 46 are preferably bonded to each other over at least a portion of the length of the channel forming region(s). This bond provides structural integrity for the channels in dry and wet conditions. This bond may be provided using any known bonding technique known in the art, particularly bonds selected from adhesive bonding, thermal bonding, mechanical bonding, ultrasonic bonding, or any combination thereof. Adhesive may be applied, for example, typically by slot glue application or any other means, into the areas of the channels on the top inside and / or bottom inside of the core wrap, and then pressure is applied to the areas of the channels to provide a good adhesive bond to these areas. Exemplary patent disclosures of such adhesive bonding processes can be found in WO 2012 / 170,798(A1) (Jackels et al.), EP 2,905,000 (Jackels et al.) and EP 2,905,001 (Armstrong-Ostle et al.) for airfelt or airfelt-free absorbent cores.
[0067] Other bonds, such as thermal, mechanical, ultrasonic, etc., may also be used as additional or alternative bonds. For example, adhesive bonds may be supplemented with thermal, mechanical, or ultrasonic bonds. Such thermal, mechanical, or ultrasonic bonds may be applied on the channels through the outside of the core wrap layer.
[0068] Typically, the channel bonds will generally have the same contour and shape as the channel forming region 26 in which they are contained, but may be slightly smaller to allow for a safety margin (e.g., only a few mm) since some deviation from optimal alignment may occur during high speed processes. The channel forming region(s) form a three-dimensional channel(s) during use as the remainder of the absorbent layer and the absorbent core swells as it absorbs fluid. The channel forming region(s) are optional in the present invention.
[0069] The total amount of SAP present in the absorbent core is adapted to the needs of the envisaged wearer of the article. Newborn diapers require less SAP than infant or adult incontinent diapers. The amount of SAP in the core may be, for example, about 2 g to 50 g, particularly 5 g to 40 g, in a typical infant diaper. The average SAP basis weight in the absorbent core is, for example, at least 50, 100, 200, 300, 400, 500 g / m 2 or more than 200g / m 2 ~400g / m 2 The average SAP basis weight can be the total amount of SAP in the core divided by the area defined by the perimeter of the SAP layer (including any channel-forming area, if present).
[0070] Superabsorbent Particles 60 Superabsorbent polymers (SAPs) are typically water-insoluble, but water-swellable crosslinked polymers that can absorb large amounts of fluid. SAPs are typically in particulate form so that they are flowable in the dry state, facilitating deposition onto a substrate. Typical SAPs are made of polyacrylate polymers, although it is not excluded that other polymeric materials may also be used.
[0071] The absorbent core of the present invention comprises at least one layer of superabsorbent polymer particles having a urine permeability measurement ("UPM") of greater than 45 UPM units, where 1 UPM unit is equal to 1×10 -7 (cm 3 ·s) / g. The UPM value is advantageously at least 50 UPM units, in particular at least 55 UPM units or at least 60 UPM units. The SAP may preferably have a UPM in the range of 55 to 90 UPM units, in particular in the range of 55 to 80 UPM units, more particularly in the range of 60 to 75 UPM units, 1 UPM unit being equal to 1×10 -7 (cm 3·s) / g. The UPM value is measured according to the Urine Permeability Measurement (UPM) method described herein. The UPM method measures the flow resistance of a pre-swollen layer of superabsorbent polymer particles, i.e. the flow resistance is measured after loading the SAP with saline. Thus, such superabsorbent polymer particles with high UPM value exhibit high permeability when a significant volume of the absorbent article is already wetted by liquid exudate.
[0072] Unless otherwise indicated, the values given herein to qualify the SAP (e.g. SAP UPM, EFFC, T20...) refer to the properties of the entire SAP forming the layer considered. For example, if two separate layers of SAP are included in the absorbent core and the SAP used is different in each layer, at least one of these should have the UPM value claimed. If the SAP layer is formed by combining two intermediate layers of SAP layers (as known for printed SAP technology, see below), which are no longer separate but form a single layer, the SAP value refers to the entire SAP forming the combined SAP layer.
[0073] The superabsorbent polymer particles preferably have an effective capacity (EFFC) of more than 23 g / g, more preferably in the range of 23 g / g to 30 g / g, especially in the range of 23.5 g / g to 29 g / g, or 24 g / g to 28 g / g, or 24.5 g / g to 27 g / g. The effective capacity (EFFC) is calculated by the following formula: EFFC=(CRC+AAP) / 2. The Centrifuge Retention Capacity (CRC) is measured by the Centrifuge Retention Capacity (CRC) Test Method described herein and the Absorption Against Pressure (AAP) is measured by the Absorption Against Pressure (AAP) Test Method described herein. The SAP of the present invention may have an AAP of at least 22 g / g, or from 23 to 24.5 g / g, or from 24.0 to 24.5 g / g.
[0074] The SAP particles further have a bulk density of at least 0.5 g / mL, measured according to the Bulk Density Test Method.
[0075] SAPs with the desired properties can be ordered from known SAP manufacturers, regardless of the manufacturing method. These SAPs used in the present invention can typically be obtained by surface crosslinking precursor SAPs. Suitable precursor SAP particles can be obtained, for example, from inverse suspension polymerization as described in WO 2015 / 041,784 (A1) or EP 2,535,027 (A1), or from US Pat. Nos. 4,340,706 and 5,849,816, or from spray-phase dispersion polymerization or other gas-phase dispersion polymerization as described in US Patent Application Publications Nos. 2009 / 0192035, 2009 / 0258994, and 2010 / 0068520. In some embodiments, suitable precursor superabsorbent polymer particles can be obtained by the production process described in more detail in WO 2006 / 083584, p. 12, line 23 to p. 20, line 27.
[0076] The precursor water-absorbing polymer particles may typically be internally crosslinked, i.e., polymerization is carried out in the presence of a compound having two or more polymerizable groups that can be free-radically copolymerized into a polymer network. Useful crosslinking agents ii) are, for example, ethylene glycol dimethacrylate, diethylene glycol diacrylate, allyl methacrylate, trimethylolpropane triacrylate, triallylamine, tetraallyloxyethanes as described in European Patent Application No. A 530 438, diacrylates and triacrylates as described in European Patent Nos. A 547 847, A 559 476 and A 632 068, WO 93 / 21237, WO 03 / 104299, WO 03 / 104300 and WO 03 / 104301 and German Patent No. A 103 31 450, German Patent Nos. A 103 31 456 and A 103 55 Mention may be made of mixed acrylates which further comprise acrylate groups and ethylenically unsaturated groups, as described in DE-A 195 43 368, DE-A 196 46 484, WO 90 / 15830 and WO 02 / 32962, or crosslinker mixtures, as described, for example, in DE-A 195 43 368, DE-A 196 46 484, WO 90 / 15830 and WO 02 / 32962.
[0077] Preferably, the internal crosslinker ii) is a di-, dimeth-, tri- or trimethacrylated polyethoxylated glycerol and / or a propoxylated glycerol. Diacrylates and / or triacrylates of 3- to 10-tuply ethoxylated glycerol are particularly advantageous. More preferably, the crosslinker ii) is a diacrylate or triacrylate of 1- to 5-tuply ethoxylated and / or propoxylated glycerol. Preferably, the internal crosslinker comprises an acrylate group or an acrylamide group.
[0078] A detailed example of the preparation of SAP according to the present invention by surface cross-linking is provided in the following section entitled "Method of Preparing SAP".
[0079] The SAP used in the present invention may be surface cross-linked. Commonly applied surface cross-linking agents are heat-activated surface cross-linking agents. The term "heat-activated surface cross-linking agent" refers to a surface cross-linking agent that reacts only when exposed to high temperatures, typically around 150°C. Heat-activated surface cross-linking agents known in the prior art are, for example, di- or polyfunctional agents capable of building additional cross-links between the polymer chains of the precursor superabsorbent polymer particles. Other heat-activated surface cross-linking agents include, for example, di- or polyhydric alcohols or derivatives thereof capable of forming di- or polyhydric alcohols. Representative examples of such agents are alkylene carbonates, ketals and di- or polyglycidyl ethers. Furthermore, (poly)glycidyl ethers, haloepoxy compounds, polyaldehydes, polyols and polyamines are also well-known heat-activated surface cross-linking agents. The cross-linking is based on a reaction between functional groups contained in the precursor superabsorbent polymer particles, for example an esterification reaction between carboxyl groups (contained in the polymer) and hydroxyl groups (contained in the surface cross-linking agent).
[0080] Generally, the surface cross-linking agent is applied on the surface of the precursor superabsorbent polymer particles.Therefore, the reaction preferably occurs on the surface of the precursor superabsorbent polymer particles, resulting in improved cross-linking on the surface of the particles without substantially affecting the core of the particles.This makes the surface of the superabsorbent polymer particles harder.
[0081] The SAP of the present invention may be surface cross-linked, for example, using an alkylene carbonate as the surface cross-linking agent, preferably using a surface cross-linking solution comprising deionized water. Preferably, the application of the surface cross-linking solution is applied by stray-coating. Heat treatment of the SAP of the present invention may be carried out at elevated temperatures, preferably above 185°C, more preferably between 190°C and 205°C.
[0082] The SAP of the present invention is preferably classified after surface cross-linking and subsequent heat treatment, for example using a sieving step. Preferably, the SAP of the present invention is sieved to a particle size range of 710 μm to 45 μm, as measured by EDANA NWSP 220.0R2 (19).
[0083] The SAP K(t) test method described below is also useful for determining other SAP parameters that may also be advantageously used in the present invention. The SAP used in the core may advantageously have a time to reach an absorption of 20 g / g (SAP T20) of less than 220 seconds as measured by the SAP K(t) test method. The SAP may specifically have a SAP T20 of 100 seconds to 220 seconds. The SAP T20 value may be less than 200 seconds, or less than 180 seconds, or less than 160 seconds. The time T20 may also be at least 100 seconds, 104 seconds, 120 seconds, or 140 seconds, and any combination of these upper and lower values forming a range, for example, from 100 seconds to 200 seconds.
[0084] The SAP uptake at 20 minutes (U20) can be, inter alia, at least 22 g / g, or at least 24 g / g, or at least 28 g / g, or at least 30 g / g, or from 28 g / g to 60 g / g, or from 30 g / g to 50 g / g, or from 30 g / g to 40 g / g, as measured according to the SAP K(t) test method disclosed herein. The SAP can be at least 1×10 -8 cm 2 , or at least 2 × 10 -8 cm 2 , or at least 2.5 × 10 -8 cm 2 , or 3 × 10 -8 cm 2 ~1×10 -7 cm 2 , or 2 × 10 -8 cm 2 ~7×10 -8 cm 2 , or 2.5 × 10 -8 ~5×10 -8 cm 2The effective permeability at 20 minutes (SAP K20) may be:
[0085] The SAP may also have a ratio of the minimum effective permeability to the permeability at 20 minutes (SAP Kmin / SAP K20 ratio) greater than 0.75, or greater than 0.8, or greater than 0.85, as measured according to the SAP K(t) test method. In such embodiments, transient gel blocking is minimal and liquid exudates can move quickly through the voids present between the particles throughout the entire swelling process, especially in the initial part of the swelling phase, which is most critical for the first gush.
[0086] The SAP of the present invention is typically selected from internally and surface crosslinked polyacrylate and polyacrylic acid polymers. The superabsorbent polymer can be internally crosslinked, i.e. the polymerization is carried out in the presence of a compound having two or more polymerizable groups that can be free-radically copolymerized into a polymer network. Exemplary superabsorbent polymer particles of the prior art are described, for example, in WO 2006 / 083584, WO 2007 / 047598, WO 2007 / 046052, WO 2009 / 155265, WO 2009 / 155264. Preferably, the SAP particles comprise crosslinked polymers of polyacrylic acid or their salts or polyacrylate or their derivatives.
[0087] SAP particles may be relatively small in their dry state (less than 1 mm in their longest dimension) and approximately circular in shape, although granules, fibers, flakes, spheres, powders, platelets, and other shapes and forms are known to those skilled in the art. Generally, SAP may be in the form of spherical particles.
[0088] At least a portion of the SAP particles may be agglomerated, for example, as taught in EP 3,391,961 (A1) (Kamphus, P&G). Agglomerated superabsorbent polymer particles may be obtained by various methods. Agglomerated particles may be obtained, for example, by agglomerating precursor particles with an interparticle crosslinking agent reacted with the polymeric material of the precursor particles to form crosslinks between the precursor particles, as disclosed, for example, in U.S. Pat. Nos. 5,300,565, 5,180,622 (both to Berg), 5,149,334, 5,102,597 (both to Roe), and 5,492,962 (Lahrman). Other methods for obtaining agglomerated SAP particles are described, for example, in EP 3056521(B1) (Kim et al.), EP 1512712(B1) (Koji et al.), U.S. Pat. No. 10414876(B2) (Jang et al.), U.S. Pat. No. 7429009(B2) (Nagasawa et al.), EP 220224911 (Higashimoto et al.), EP 2011803(B1) (Handa et al.).
[0089] Agglomerated superabsorbent polymer particles can also be obtained by a process comprising the steps of providing superabsorbent polymer particles and mixing the superabsorbent polymer particles with a solution comprising water and a multivalent salt having a valence of 3 or more. This process is further disclosed in EP 2,944,376 A1. The superabsorbent polymer particles may specifically comprise at least 5% by weight of SAP, or at least 10% by weight, or at least 20% by weight, or at least 30% by weight, or at least 40% by weight, or at least 50% by weight of SAP. A process for the preparation of agglomerated superabsorbent polymer particles comprising edge-modified and / or surface-modified clay platelets is disclosed in EP 3391963.
[0090] The surface of the SAP particles may be coated. The SAP may also comprise surface-modified and / or edge-modified clay platelets. Preferably, the clay platelets are montmorillonite, hectorite, laponite, or mixtures thereof. Preferably, the clay platelets are laponite. The SAP may comprise 0.1-5 wt. % of surface- and / or edge-modified clay platelets compared to the weight of the precursor superabsorbent polymer particles.
[0091] Upward Acquisition and Distribution System ("Upward ADS") With reference to Figures 1 and 2, the absorbent article 20 of the present disclosure comprises an upper acquisition and distribution system (referred to herein as "upper ADS"). The ADS encompasses all layers 52, 54 (one or more layers) disposed between the topsheet 24 and the absorbent core 28. The upper ADS can rapidly acquire body fluids, such as urine, and efficiently distribute it to the absorbent core 28. The upper ADS may include a single layer or may have two or more layers, which may form a unitary structure or may remain separate layers, which may be attached to each other, for example, by thermal bonding, adhesive bonding, or a combination thereof. Unitary structure in this specification is intended to mean that the sublayers may be formed of several sublayers having properties and / or compositions distinct from each other, but which are somehow intermingled with each other at the boundary regions, such that instead of clear boundaries between the sublayers, it is possible to distinguish the regions where the different sublayers transition into each other. Such unitary structures are typically constructed by forming different sub-layers one on top of the other in a continuous fashion, for example using airlaid or wetlaid deposition. Typically, no adhesive is used between the sub-layers of the unitary material. In some cases, however, adhesives and / or binders may be present in lesser amounts than in multi-layer materials that are typically formed by separate layers.
[0092] As indicated above, crosslinked cellulose fibers have been used in the art to form distribution layers deposited on latex-bonded nonwoven acquisition layers. Such crosslinked cellulose fibers are not bonded to one another and, in contrast to nonwoven or airlaid layers, the crosslinked cellulose fibers have no inherent integrity, which can cause the crosslinked cellulose fibers to form clumps during use, reducing the benefits of such distribution layers.
[0093] According to the invention, the upper ADS is substantially free of unbonded crosslinked cellulose fibers. By "substantially free" we mean that such crosslinked cellulose fibers form less than 20% by weight, preferably less than 10% by weight, of the upper ADS, more preferably the upper ADS does not contain any unbonded crosslinked cellulose fibers. More generally, the upper ADS preferably consists of one or more nonwoven layers. The upper ADS is preferably free of unbonded cellulose fibers, but may contain cellulose fibers formed into a web, such as an airlaid nonwoven layer comprising a mixture of cellulose and synthetic fibers.
[0094] The upper ADS may comprise two layers: a first layer 52 directly under the topsheet and a second layer 54 between the first layer and the absorbent core. An example of a suitable dual-layer ADS is disclosed in US20210106471(A1) (Yuan et al., P&G), which discloses a first layer that is a carded air-through nonwoven and a second layer that is an airlaid nonwoven. Without being bound by theory, the thermoplastic fibers provide a more open structure while improving the structural integrity of the fluid distribution layer. The cellulosic fibers provide liquid storage capacity and a resilient open structure that allows the fluid distribution layer to recover quickly even after repeated rough handling.
[0095] The first layer 52 may be an acquisition nonwoven layer as known in the art, such as an air-through bonded carded nonwoven having a basis weight of, for example, 20 gsm to 100 gsm, particularly 30 gsm to 80 gsm. Such acquisition layers are typically made of synthetic fibers that have been hydrophilically treated with a surfactant. The acquisition layer 52 may also be a latex bonded, hydrophilically treated nonwoven.
[0096] The second layer 54 of the upper ADS, if present, may be selected from a variety of nonwoven materials, such as airlaid nonwovens comprising a mixture of cellulosic and synthetic fibers combined to form a single nonwoven web.
[0097] The second layer 54 may also include or consist of a spunlace nonwoven, which has been found to provide good fluid handling, integrity, and flexibility. Suitable spunlace may have a basis weight ranging from about 40 grams per square meter (gsm) to about 200 gsm, preferably from about 70 gsm to about 120 gsm. Spunlace typically includes a plurality of absorbent fibers, a plurality of stiffening fibers, and a plurality of elastic fibers integrated into the spunlace. Spunlace is -about 20 percent to about 75 percent absorbent fibers; - about 1 percent to about 50 percent stiffening fibers; - about 10 percent to about 50 percent elastic fibers.
[0098] Examples of suitable spunlace are disclosed, for example, in WO 2020 / 205,485(A2) (Peri et al., P&G).
[0099] Other materials for the second layer are also possible, such as a spunbond or spunbond-meltblown-spunbond ("SMS") nonwoven. SMS can refer to a 3-ply "sms" nonwoven material, a 5-ply "ssmms" nonwoven material, or any reasonable variation thereof, with lower case letters indicating individual layers and upper case letters indicating an organization of similar adjacent layers.
[0100] The upper ADS of the present invention typically does not include superabsorbent materials. The upper ADS of the present invention may have an overall basis weight, calculated on an average over the entire area of the upper ADS, ranging from about 20 gsm to about 220 gsm, particularly from about 40 gsm to about 160 gsm. In some embodiments, the upper ADS according to the present invention comprises cellulosic fibers of less than about 40 gsm. The basis weight of the first layer may be determined to balance acquisition and distribution performance with the overall thickness of the absorbent article. If the upper ADS includes an acquisition layer 52 and a distribution layer 54, the distribution layer may typically have a basis weight about the same as or higher than the acquisition layer. Basis weight can be calculated as usual by dividing the weight of the layer by its area.
[0101] Lower Acquisition and Distribution Layer (Lower "ADL") 56 The articles of the present invention may optionally include an acquisition distribution layer (herein referred to as the "lower ADL") between the layer of SAP and the backsheet. The use of a lower ADL is optional to provide additional temporary storage while minimizing or preventing the perception of moisture from the outer surface of the absorbent article.
[0102] The lower ADL 56 is typically provided between the absorbent core 28 and the backsheet, as depicted in Figure 3A. In other words, the lower ADL is typically disposed between the lower core wrap layer 46 and the liquid impermeable backsheet 25. This structure is also the simplest to manufacture, since no changes are required to the existing absorbent core manufacturing process, and the lower ADL is additionally inserted between the absorbent core and the backsheet.
[0103] Alternatively, it is also contemplated that the lower ADL 56' may, in some cases, be used as the lower core wrap layer 46 and may be in direct contact with the layer of SAP 60 (so that there is no separate lower core wrap layer 46). In this case, the upper core wrap layer 45 and the lower ADL 56' may partially or completely surround the SAP layer 60. This embodiment is shown in FIG. 3B for an alternative absorbent article 20'. In this construction, the core wrap is formed by the upper core wrap layer 45 and the lower ADL 56'. However, such a construction has a drawback because the lower ADL 56' needs to be larger and longer than necessary to cover the entire layer of absorbent material 28, which has additional material costs. The basis weight, and therefore material cost, of the lower ADL is typically a multiple of the low basis weight SMS nonwoven that can be used as the lower core wrap layer 46. Therefore, it may be preferred that the absorbent article comprises a lower core wrap layer 46 and a separate lower ADL 56, as shown in FIGS. 3A and 3C.
[0104] In another alternative, as shown in Figure 3C, the SAP absorbent material 60 and the lower ADL 56" may be partially or completely encapsulated between the upper core wrap layer 45 and the lower core wrap layer 46. The lower acquisition and distribution layer 56" is disposed between the layer of SAP 60 and the lower core wrap layer 46 in this alternative and is therefore integrated into the absorbent core. However, this embodiment adds complexity to the core manufacturing process and does not exclude the possibility that some superabsorbent particles may penetrate the pores of the ADL and affect its fluid handling properties.
[0105] The lower ADL may consist of a single layer, as shown, in particular a single nonwoven layer having the required properties. Alternatively, it is not excluded that the lower ADL may be a multi-layer structure such as a laminate, or an integrated layer including integrated sub-layers, so long as the multi-layer structure has the required properties. Such a multi-layer structure may also include two sub-layers, each having a different width, such that the lower ADL has an increased basis weight in the central longitudinally extending region of the article where both sub-layers are present. For the avoidance of doubt, when the absorbent article comprises a separate lower core wrap layer 46, the basis weight is 20 g / m 2 Any such separate lower core wrap layer having a basis weight less than is not considered part of the lower ADL.
[0106] The lower ADL 56 may include or consist of a nonwoven layer, which can act as a temporary reservoir for liquid that has flowed through the layer of SAP because it has not been absorbed quickly enough by the absorbent material.
[0107] Additional layers provided in absorbent articles generally increase the thickness and bulk of the article, thus reducing the comfort of the wearer. Also, increased bulk, especially between the legs of the wearer, is generally undesirable. Therefore, it may be desirable to limit the caliper of the lower ADL to within 0.3 mm, optionally, for example, up to 4 mm, measured at a pressure of 0.85 kPa according to the caliper measurement method described herein.
[0108] The basis weight of the lower ADL is typically (but not necessarily) 20 g / m 2 ~100g / m 2 , or 25 g / m 2 ~80g / m 2 , or 30 g / m 2 ~50g / m 2The basis weight of the lower ADL, at least when comprised of a single layer, is typically homogenous throughout the length and width of the lower ADL (i.e., longitudinally and transversely). The basis weight of a material is typically provided by a supplier and can also be calculated by dividing the weight of the lower ADL by its surface area.
[0109] The lower ADL may have a smaller longitudinal and / or transverse extension than the layer of SAP 60, such that the layer of absorbent material extends longitudinally and / or transversely beyond the lower ADL. The SAP layer 60 may also extend longitudinally and / or transversely beyond the upper ADS.
[0110] Alternatively, the lower ADL may have a greater longitudinal and / or transverse extension than the layer of absorbent material, such that the lower ADL extends longitudinally and / or transversely beyond the layer of absorbent material. This may be desirable when the layer of absorbent material is in direct contact with the lower ADL (i.e., there is no lower substrate layer between the layer of absorbent material and the lower ADL), as shown in Figure 3B. In such a configuration, the layer of SAP may be disposed over either the upper core wrap layer 46 or the lower ADL 56, or partially over each layer.
[0111] The lower ADL may preferably not contain superabsorbent polymer. The lower ADL may comprise or consist of a nonwoven layer. The nonwoven layer may be any type of conventional nonwoven fabric and fiber, as long as the required properties are met. It has been found that carded nonwoven fabrics (made from staple fibers) are particularly suitable. The carded nonwoven fabric may be calender bonded or air-through bonded, as known in the art. The nonwoven layer may also be a spunbond or meltblown nonwoven web (made from continuous fibers), or a nonwoven fabric with spunbond and meltblown layers (e.g., SMS, SMMS, SMSS, etc.).
[0112] Air-through bonded nonwovens generally have high loft. Thus, they have a porous structure to provide void volume for absorbing and temporarily retaining liquid. At the same time, they provide softness and do not have excessively high bending stiffness.
[0113] The lower ADL may comprise at least 30% by weight, optionally at least 50% by weight, and up to 100% by weight, of crimped fibers based on the total weight of the lower acquisition and distribution layer. The crimped fibers may have two-dimensional crimp, three-dimensional crimp, or a combination of two-dimensional and three-dimensional crimp. Typically, in a carding process, all or most of the fibers are crimped in two dimensions (zigzag), whereas the eccentric bicomponent fibers may typically be crimped in three dimensions. The crimped fibers may help drive the loft and void volume of the nonwoven.
[0114] The ADL layer, particularly the nonwoven layer thereof, may be made of or consist of synthetic fibers. In particular, suitable synthetic fibers are made of polyolefins (e.g., polyethylene, polypropylene, or mixtures or combinations thereof), polyethylene terephthalate (PET), co-PET, polylactic acid (PLA), polyhydroxyalkanoid (PHA), or combinations or mixtures thereof. The fibers may be continuous or staple fibers.
[0115] The fibers can be monocomponent fibers or multicomponent fibers, such as bicomponent fibers. When the fibers included in the lower ADL are bicomponent fibers, they have a core-sheath configuration, with the core component having a higher melting point than the sheath component.
[0116] The fibers included in the lower ADL are preferably staple fibers. Similar to nonwoven webs made with continuous fibers, the staple fiber nonwoven webs are preferably air-through bonded. In addition to hydroentanglement (spunlace) or air-through bonding, the staple fiber nonwoven webs may or may not be subjected to some localized bonding with heat and / or pressure (e.g., point bonding / calendar bonding) to introduce localized bond areas where the fibers are fused together.
[0117] Regardless of whether the nonwoven web is made of continuous or staple fibers, the localized bonding, however, must not bond too much surface area and thus adversely affect the loft and void volume of the nonwoven web. Preferably, the total bond area provided by localized bonding with heat and / or pressure (in addition to hydroentanglement or air-through bonding) should not be greater than 20%, or greater than 15%, or greater than 10% of the total surface area of the nonwoven web.
[0118] Through-air bonding (used interchangeably with the term "air-through bonding") refers to the process of bonding staple or continuous fibers by forcing air through the nonwoven web, where the air is hot enough to melt (or at least partially melt, or melt until the surface of the fiber is sufficiently tacky) the polymer of the fiber, or, if the fiber is a multicomponent fiber, the air is hot enough to melt (or at least partially melt, or melt until the surface of the fiber is sufficiently tacky) one of the polymers from which the fibers of the nonwoven web are made. Air speeds are typically 30 to 90 meters per minute, and residence times can be up to 6 seconds. The melting and resolidification of the polymer provides the bond between the different fibers.
[0119] The hot air melts the staple or continuous fibers, or, in the case of multicomponent fibers, the lower melting polymer component of the fibers, thereby forming bonds between the staple fibers to consolidate and integrate the layers of staple fibers into a web.
[0120] The lower ADL may include multicomponent fibers that at least partially form the nonwoven. The fibers of the nonwoven included in the lower ADL may include at least 30% by weight, or at least 40% by weight, or at least 50% by weight, or at least 70% by weight, or at least 90% by weight, or 100% by weight of multicomponent fibers, based on the total weight of the nonwoven included in the lower acquisition and distribution layer. The multicomponent fibers may be bicomponent fibers, such as core-sheath or side-by-side bicomponent fibers.
[0121] Alternatively, the nonwoven layer included in or forming the lower ADL may comprise monocomponent fibers. The fibers of the nonwoven included in the lower acquisition and distribution layer may comprise at least 30%, or at least 40%, or at least 50%, or at least 70%, or at least 90%, or 100% by weight of monocomponent fibers, based on the total weight of the nonwoven included in the lower acquisition and distribution layer. The nonwoven web included in or forming the lower ADL may comprise a mixture of monocomponent and multicomponent fibers.
[0122] In general, the fiber dtex (related to the diameter of the fiber) directly affects the pore size of the material and therefore, in particular, the capillary pressure and the permeability / wetting of the material and the wetting out of the material. For a given basis weight, the lower the dtex, the lower the permeability and the higher the capillary pressure. The lower acquisition and distribution layer may comprise fibers having at least 50% by weight, or at least 70% by weight, or at least 80% by weight, and up to 100% by weight, of fibers with a denier below 10 dtex.
[0123] In particular, when the lower ADL comprises or consists of synthetic fibers that are hydrophobic in nature, the lower ADL may advantageously comprise a hydrophilic agent. Any conventional hydrophilic treatment that provides a hydrophilic agent may be used. Typically, webs such as nonwovens may be coated on the outside with a surfactant directly or via an oil / emulsion. Alternatively, as known in the art, a hydrophilic melt additive may be added in the polymer melt used to make the fibers. The hydrophilic melt additive is an amphiphilic molecule with a hydrophilic head and a hydrophobic tail. The hydrophilic head is oriented towards the surface of the adhesive, thus providing the hydrophilic character of the adhesive, while the hydrophobic head remains in the polymer matrix.
[0124] Hydrophilic melt additives are typically incorporated into a masterbatch in the form of pellets rather than being incorporated by homogeneous mixing in molten polyolefin. Commercially available examples of hot melt additives that are particularly compatible with propylene-based metallocene-catalyzed polyolefins are PPM 15560 (hydrophilic PP masterbatch) from Techmer, and Brij S2 (Croda). In addition, Brij S10 (Croda), Unithox 450, Unithox 720, and Unithox 750 (Baker Hughes) can be used in decreasing order of preference. PPM 15560 is preferably used at a dosage of 0.5 weight percent of the masterbatch, and Brij S2 and Brij S10 are preferably used at a dosage of 2 weight percent of active material. Techmer's Techsurf® melt additive has been used to impart hydrophilicity to polyolefin fibers, nonwovens, and specialty plastic applications, and is useful in the present invention.
[0125] No. 6,146,757 discloses a hydrophilic melt additive comprising a blend of a first wetting agent and a second wetting agent, the first wetting agent being at least one water-insoluble nonionic alkoxylated alkylphenol, and the second wetting agent being at least one compound selected from the group consisting of alkoxylated fatty alcohols and water-soluble, nonionic, non-hydrolyzable polyoxyalkylene-modified organosilicone polymers.
[0126] The lower ADL 56 and the lower core wrap layer 46 may advantageously both be hydrophilic. The lower ADL may optionally be less hydrophilic than the lower core wrap layer.
[0127] package A plurality of absorbent articles according to the present invention may be packaged in a package for shipping and sale. At least 50% of the articles in the package, preferably all of the articles, may be according to the present invention. The articles may be folded and packaged as known in the art. The package may be, for example, a plastic bag or a cardboard box. Diapers are typically folded in two along a transverse axis and the ears may be folded inwardly before packaging. The absorbent articles may be packaged under compression to reduce the size of the package while providing an appropriate number of absorbent articles per package. Packaging the absorbent articles under compression may allow the caregiver to easily handle and store the package while at the same time providing the manufacturer with reduced distribution costs due to the size of the package.
[0128] Thus, the absorbent article may be compressed and packaged with an in-bag compression ratio of at least 10%, particularly 10% to 50%, particularly 20% to 40%. As used herein, "in-bag compression ratio" is 1 minus the stack height ("in-bag stack height" or "IBSH") measured under compression in a bag of 10 folded articles divided by the stack height of 10 folded articles of the same type before compression, multiplied by 100, i.e. (1-IBSH / pre-compressed stack height) x 100 reported as a percentage. Of course, an in-bag stack need not have exactly 10 articles, but rather is the measured stack height of the articles in the package multiplied by the number of articles in the stack, then multiplied by 10. The method used to measure the in-bag stack height is described in more detail in the test procedure. Pre-compressed articles are sampled from the production line between the folding unit and the stack packaging unit. The pre-compression stack height is measured by taking 10 articles before compression and packaging and measuring their stack height as shown for IBSH.
[0129] The absorbent article packages of the present disclosure may have in-bag stack heights of less than 110 mm, less than 105 mm, less than 100 mm, less than 95 mm, less than 90 mm, specifically all of the ranges specified, and all 0.1 mm increments within or formed by the ranges specified (the in-bag stack height test is described in detail in U.S. Patent Application Publication No. 2014 / 0143180(A1)). For each of the values set forth in the previous sentence, it may be desirable to have in-bag stack heights of greater than 60, or greater than 70 mm, or greater than 75 mm, or greater than 80 mm. Alternatively, a package of absorbent articles of the present disclosure may have an in-bag stack height of 60 mm to 110 mm, 65 mm to 110 mm, 70 mm to 110 mm, 75 mm to 105 mm, or 80 mm to 100 mm, specifically all of the ranges specified and all 0.1 mm increments within or formed by the specified ranges.
[0130] Bio-sourced materials The components of the disposable absorbent articles of the present invention (i.e., diapers, pants, sanitary napkins, panty liners, etc.) may be any of the compositions and methods described in U.S. Patent Application Publication Nos. 2007 / 0219521(A1) published on September 20, 2007 to Hird et al., 2011 / 0139658(A1) published on June 16, 2011 to Hird et al., and 2011 / 0139658(A1) published on June 16, 2011 to Hird et al. No. 0139657(A1), Hird et al., published June 23, 2011, No. 2011 / 0152812(A1), Hird et al., published June 16, 2011, No. 2011 / 0139662(A1), Hird et al., published June 16, 2011, and No. 2011 / 0139659(A1), Hird et al., published June 16, 2011. These components include, but are not limited to, the topsheet nonwoven, the backsheet film, the backsheet nonwoven, the barrier leg cuff nonwoven, the superabsorbent material, the upper and lower core wrap layers, the adhesive, the fastener hooks, and the fastener landing zone nonwoven, and the film base. For example, the upper and / or lower acquisition and distribution layers of the present invention may at least partially comprise biosourced inclusions.
[0131] Components of disposable absorbent articles may comprise a biobased content value of from about 10% to about 100% using ASTM D6866-10, Method B, in other embodiments from about 25% to about 75%, and in yet other embodiments from about 50% to about 60% using ASTM D6866-10, Method B.
[0132] To apply the ASTM D6866-10 methodology to determine the biobased content of any disposable absorbent article component, a representative sample of the disposable absorbent article component must be obtained for testing. The disposable absorbent article component can then be ground to fine particles of less than about 20 mesh using known grinding methods (e.g., a Wiley® mill) and a representative sample of suitable mass can be removed from the randomly mixed particles.
[0133] Examples and Data SAP material: Table 1 below shows the properties of the different SAPs used to make the diaper examples. Comparative Example SAP1 ("COMP SAP1") and Comparative Example SAP2 ("COMP SAP2") were both Aquaic CA L825 from Nippon Shokubai Co., Ltd. of Himeji, but were taken from different packages. The properties were measured as further indicated in the "Test Methods" section below.
[0134] [Table 1]
[0135] SAP1-5 according to the invention were obtained by surface cross-linking of either COMP SAP1 or COMP SAP2 in order to increase the urinary permeability measurement ("UPM") values. As can be seen from this Table 1, surface cross-linking can significantly increase the UPM values while moderately decreasing the EFFC. A detailed description of the cross-linking method is further described below in the section "Method of making SAP1-5".
[0136] Examples of absorbent articles with lower ADL COMP SAP1, SAP1 and SAP2 were used to hand make absorbent articles in the form of diapers containing an airfelt-free core (as commercially used in Pamper® diapers). All diapers had a 30 gsm air-through bonded (ATB) acquisition layer and 50 gsm spunlace (SL) as the distribution layer. A lower ADL (carded air-through bonded "C-TAB") was also placed between the absorbent core and the backsheet. The only difference between the four diaper examples tested was the nature and amount of SAP used in the absorbent core, as shown in Table 2 below.
[0137] The diapers thus obtained were tested according to the C-SABAP method (Curved-Speed of Acquisition with Balloon Applied Pressure). C-SABAP determines the time required to acquire a given amount of saline while the diaper is held in a slightly curved position, placed on a latex film inflated by compressed air at 2.07 kPa (0.30 psi) and monitored by a digital pressure gauge. The speed of acquisition was measured in four replicates for each type of diaper. Four spurts of colored saline (0.9 wt%), each 75 mL, were applied sequentially at a rate of 15 mL / s with 5 minutes between each spurt. The acquisition time of each spurt is recorded from the time fluid application began to the time when no fluid is present on the surface of the TS over the application area. The liquid is delivered to the diaper 102 mm from the front of the absorbent core and centered in the transverse direction. Lower acquisition time figures are desirable and indicate a faster absorption rate of the absorbent article.
[0138] The acquisition times in seconds for these four successive saline spurts were measured for eight diapers per leg and the average results are shown in Table 2 below with the standard deviation in parentheses.
[0139] [Table 2]
[0140] As can be seen from Table 2, the diapers of the present invention (Examples 2-4) have shorter first acquisition times with SAPs having UPM values greater than 50 UPM units. Examples 2 and 3 further provided comparable performance for the second, third and fourth squirts, even with lower or equivalent total core EFFC values relative to Comparative Example 1. Example 3 has the same total EFFC as Comparative Example 1, but exhibits shorter acquisition times for each of the four squirts.
[0141] The data shows that at comparable total core capacity (total core EFFC), higher permeability SAPs are more effective at reducing acquisition time. Even at lower total core EFFC, acquisition speed could be at least partially improved over comparative SAPs. Without being bound by theory, it is believed that an appropriate balance of capacity and permeability can provide the desired performance for airfelt-free diapers with upper acquisition systems that do not include unbonded crosslinked cellulose fibers.
[0142] Absorbent article without lower ADL Further test diapers were hand made using COMP SAP2, SAP3, SAP4, and SAP5 as shown in Table 3 below and tested as previously indicated. The acquisition layer was a 43 gsm resin bonded (RB) carded nonwoven. The distribution layer was a 75 gsm spunlace with 40% 1.3 dtex viscose, 30% 4.4 dtex PET / CoPET, and 30% 10 dtex PET HS. The diapers in this series of tests did not have a lower acquisition and distribution layer.
[0143] [Table 3]
[0144] Inventive Examples 6 and 7 show that using a SAP with a higher UPM provides equivalent acquisition rates for the four blowouts tested, even though the total core EFFC is significantly lower than Comparative Example 5.
[0145] Example 8 uses SAP3 with a very high UPM value, but the recorded capture rate is not significantly different from the previous Examples 6 and 7, or is slightly lower than in the case of the fourth capture time. Example 9 shows that it was possible to significantly improve performance by spending 1.6 g of additional SAP3. Without wishing to be bound by theory, it is believed that for a given SAP, EFFC and UPM are roughly inversely correlated. Thus, SAP3 has a very high permeability, but its EFFC is significantly lower than, for example, SAP4 or SAP5, resulting in an overall lower core capacity at an equal amount of SAP. Lower core capacity can be a problem for loading situations.
[0146] Example 6 provided the best balance between reduced capacity and increased permeability while using 0.3 g less SAP than Example 5. The performance sweet spot appears to be found at about 50 to about 100 UPM units, preferably about 55 to about 90 UPM units, where it is possible to reduce the amount of superabsorbent material without affecting the performance of the absorbent core.
[0147] How to make SAP1-5 Examples SAP1 to SAP5 of the present invention were obtained by surface cross-linking treatment of COMP SAP1 and COMP SAP2 with ethylene carbonate (EC) (application of a surface cross-linking agent in a fluidized bed), as described in detail below.
[0148] Laboratory conditions: Ambient conditions: 23±2°C and relative humidity 45±10%.
[0149] Surface cross-linking chemicals: EC: Ethylene carbonate ("EC") anhydride, 99% purity / Sigma-Aldrich.
[0150] Device: ProCell Labsystem Pro from Glatt Ingenieurtechnik GmbH, equipped with Coater Module GF3 (reactor [B206010] with process insert [B203010]), transition housing [B203000] and Wurster insert (diameter 70 mm and height 190 mm), Wurster bottom "type B" and cyclone [F121490], or similar equipment.
[0151] The spray nozzle was a two stream bottom spray nozzle (Schlick two stream nozzle, model #970 form 0S4). The nozzle cap position is adjusted so that it is flush with the tip of the nozzle pipe. Project Number: W51505 in 2013.
[0152] The system is operated without a feedback flow of fines from the cyclone.
[0153] Pump: Ismatec pump ISM404B with pump head ISM720A.
[0154] Hose: Silicone (peroxide cured) ID=2.06mm
[0155] Preparation of 300 g of surface crosslinker solution: The original bottle of EC was placed in a circulating oven at 60° C. for 2 hours to obtain a liquid form. A quantity of 299.93 g of deionized water was placed in a beaker equipped with a magnetic stirrer. A pipette with a Combitip advanced was used to measure 0.057 cm 3 An amount of EC (equivalent to 0.080 g) was taken from the bottle and transferred to a beaker.
[0156] The solution was stirred at room temperature for 5 minutes.
[0157] From the prepared solution, 264 g was taken and transferred to another beaker for coating. The beaker containing the EC aqueous solution was placed on a balance during the coating operation to control the spray rate of the coating.
[0158] Equipment preparation: Before starting coating, the equipment is started up with the pressurized air valve open. The equipment is operated at a set point of 70°C for the fluidizing air and 65 Nm 3 The mixture was preheated for about 30 minutes with an air flow rate of 100 / h.
[0159] Pump Calibration: A peristaltic pump with a silicone hose is calibrated to a flow rate of 2.5 g / min ± 0.1 g / min using approximately 20 g of deionized water.
[0160] coating: 600.0 g±1.0 g of starting SAP (COMP SAP1) was placed in a GF3 process vessel.
[0161] The device was closed and started in the following order at each setting: 1) Start the fan and set it to 65Nm 3 / h and product temperature was set at 70°C. 2) Nozzle air was started at 1.2 bar atomizing pressure. 3) Heating was started (product temperature set point 70° C.). 4) Once the temperature inside the coating vessel reached approximately 70°C, the liquid port of the spray nozzle was connected to the ethylene carbonate solution via a hose attached to the pump head and the pump was started. The solution was sprayed onto the Comp AGM 1 in the reactor at a spray rate of approximately 2.5 g / min ± 0.1 g / min. For the duration of the experiment, the product temperature was controlled within the range of 68°C to 72°C and the fluidizing air flow rate was controlled at 60-70 m 3 The spray rate of the coating agent, the fluidizing air temperature or product temperature, and the fluidizing air flow rate were set so that the water-absorbing polymer particles did not become sticky and did not require additional drying after coating was completed.
[0162] In total, 264.0 g±0.2 g of the EC solution in water was sprayed onto the Comp AGM 1 during coating. The machine was then shut down as follows. 1) The heater was turned off. 2) The fan was stopped. 3) The nozzle air injection was stopped. 4) The coated water-absorbing polymer particles were discharged from the reaction vessel into a stainless steel bowl and weighed to the nearest 0.1 g. The material in the expansion chamber above the reaction vessel and in the seal area between the reaction vessel and the expansion chamber are not collected and are discarded. If the weight of the coated water-absorbing polymer particles collected in the stainless steel bowl deviates by more than 15% by weight from the weight of the Comp AGM (here 600.0 g ± 1.0 g), the material should be discarded and the experiment repeated.
[0163] Heating / curing: The coated water-absorbing polymer particles were uniformly distributed on two Teflon-coated baking trays (41 x 31 x 10 cm). The baking trays were covered with aluminum foil and transferred to a circulating oven preheated to 192°C. The temperature in the oven was controlled within the range of 191-193°C. The coated water-absorbing polymer particles remained in the oven for the curing times listed in Table 3 below. The coated water-absorbing polymer particles were then removed from the oven and allowed to cool to room temperature while remaining on the aluminum foil-covered trays.
[0164] After the coated water-absorbing polymer particles are cooled to room temperature, they are sieved through a sieve with a diameter of about 20 cm. A stack of sieves with the following mesh sizes (in order from top to bottom): 710 μm, 45 μm, and a collection pan are used. The superabsorbent particle sample is placed on the top sieve (i.e., 710 μm) and sieved through a sieving machine (e.g., "AS 400 Control" available from Retsch GmbH, Haan, Germany) at 1 mm / g for 3 minutes.
[0165] The fraction of coated water-absorbing polymer particles between 45 μm and 710 μm in size represents each SAP sample listed in Table 1.
[0166] After sieving, SAP pre2 was heat treated / cured once more in a circulation oven. The oven was preheated to 192°C. The temperature in the oven is controlled within the range of 191-193°C. The resulting sample is SAP2, and the total heat treatment / curing time is 102 minutes.
[0167] [Table 4]
[0168] NOTE: The desired UPM level can be easily adjusted by a longer or shorter duration of heat treatment / curing, with a longer heat treatment / curing duration resulting in a higher UPM, i.e., a higher SAP permeability.
[0169] SAP3-5 were obtained similarly to SAP1-2, but starting from COMP SAP 2 and using the following curing conditions:
[0170] [Table 5]
[0171] Test Method Centrifuge Retention Capacity (CRC) Test Method CRC measures the fluid absorbed by superabsorbent polymer particles that are free swollen in excess saline. CRC is measured according to EDANA method NWSP 241.0.R2(19).
[0172] Absorbency Against Pressure (AAP) Test Method The AAP is measured in accordance with EDANA method NWSP 242.0.R2(19) at an applied pressure of 0.7 psi.
[0173] Effective Capacity (EFFC) The available capacity represents the average of the Centrifuge Retention Capacity (CRC) value and the Absorption Against Pressure (AAP) value of the superabsorbent polymer particles.
[0174] Effective capacity (EFFC) is calculated by the following formula: EFFC=(CRC+AAP) / 2.
[0175] Bulk Density Test Method For the bulk density test method, refer to EDANA Method NWSP 251.0.R2(19).
[0176] Urine permeability measurement (UPM) method Laboratory conditions: The test must be carried out in a climatized room at standard conditions of 23°C ± 2°C and 45% ± 10% relative humidity.
[0177] Urine permeability measurement system This method measured the permeability of the swollen hydrogel layer 1318. The equipment used for this method is described below.
[0178] FIG. 7 shows a transmittance measurement system 1000 including a constant hydrostatic head reservoir 1014, an open tube 1010 for air intake, a vent 1012 with a stopper for refilling, a laboratory rack 1016, a conduit 1018 with a flexible tube 1045 with a Tygon tube nozzle 1044, a stopcock 1020, a cover plate 1047, and a support ring 1040, a receiving vessel 1024, a balance 1026, and a piston / cylinder assembly 1028.
[0179] 8 shows the piston / cylinder assembly 1028, including a metal weight 1112, a piston shaft 1114, a piston head 1118, a lid 1116, and a cylinder 1120. The cylinder 1120 is made of clear polycarbonate (e.g., Lexan®) and has an inner diameter p of 6.00 cm (area = 28.27 cm 2) and the inner cylinder wall 1150 is smooth. The bottom 1148 of the cylinder 1120 is faced with a stainless steel screen cloth (ISO 9044 material 1.4401, mesh size 0.038 mm, wire diameter 0.025 mm) (not shown) that is biaxially stretched to tension before being attached to the bottom 1148 of the cylinder 1120. The piston shaft 1114 is made of transparent polycarbonate (e.g., Lexan®) and has an overall length q of about 127 mm. The central portion 1126 of the piston shaft 1114 has a diameter r of 22.15 (±0.02) mm. The upper portion 1128 of the piston shaft 1114 has a diameter s of 15.8 mm and forms a shoulder 1124. The lower portion 1146 of the piston shaft 1114 has a diameter t of approximately 5 / 8 inch (15.9 mm) and is threaded to screw securely into the central bore 1218 (see FIG. 9) of the piston head 1118. The piston head 1118 is drilled and made of clear polycarbonate (e.g., Lexan®) and is covered with a stainless steel screen cloth (ISO 9044 material 1.4401, mesh size 0.038 mm, wire diameter 0.025 mm) that has also been stretched (not shown). The weight 1112 is stainless steel, has a central bore 1130, and slides onto the top 1128 of the piston shaft 1114 and rests on a shoulder 1124. The combined weight of the piston head 1118, piston shaft 1114, and weight 1112 is 596 g (± 6 g), which corresponds to 0.30 psi across the interior area of the cylinder 1120. The total weight can be adjusted by drilling a blind hole in the central axis 1132 of the piston shaft 1114 to remove material and / or by providing a cavity and adding weight. The cylinder lid 1116 has a first lid opening 1134 at its center for vertically aligning the piston shaft 1114 and a second lid opening 1136 near the edge 1138 for introducing fluid from the constant hydrostatic head reservoir 1014 into the cylinder 1120.
[0180] A first linear index mark (not shown) is scribed radially along the top surface 1152 of the weight 1112, the first linear index mark being transverse to the central axis 1132 of the piston shaft 1114. A corresponding second linear index mark (not shown) is scribed radially along the top surface 1160 of the piston shaft 1114, the second linear index mark being transverse to the central axis 1132 of the piston shaft 1114. A corresponding third linear index mark (not shown) is scribed along the central portion 1126 of the piston shaft 1114, the third linear index mark being parallel to the central axis 1132 of the piston shaft 1114. A corresponding fourth linear index mark (not shown) is scribed radially along the top surface 1140 of the cylinder lid 1116, the fourth linear index mark being transverse to the central axis 1132 of the piston shaft 1114. Additionally, a corresponding fifth linear index mark (not shown) is scribed along the lip 1154 of the cylinder lid 1116, with the fifth linear index mark parallel to the central axis 1132 of the piston shaft 1114. A corresponding sixth linear index mark (not shown) is scribed along the outer cylinder wall 1142, with the sixth linear index mark parallel to the central axis 1132 of the piston shaft 1114. The alignment of the first, second, third, fourth, fifth, and sixth linear index marks allows the weight 1112, piston shaft 1114, cylinder lid 1116, and cylinder 1120 to be repositioned in the same orientation relative to one another for each measurement.
[0181] The detailed specifications of cylinder 1120 are as follows: Outer diameter of cylinder 1120 u: 70.35mm (±0.05mm) Inner diameter of cylinder 1120: 60.0 mm (±0.05 mm) Height of cylinder 1120 ν: 60.5 mm. The height of the cylinder must not be less than 55.0 mm.
[0182] The detailed specifications of the cylinder lid 1116 are as follows: Outer diameter of cylinder cover 1116: 76.05mm (±0.05mm) Inner diameter of cylinder cover 1116: 70.5mm (±0.05mm) Thickness y of cylinder lid 1116, including lip 1154: 12.7 mm Thickness of cylinder cover 1116 excluding lip 1154: 6.35 mm Diameter of first lid opening 1134: 22.25 mm (±0.02 mm) Diameter b of second lid opening 1136: 12.7 mm (±0.1 mm) Distance between the center of the first lid opening 1134 and the center of the second lid opening 1136: 23.5 mm
[0183] The detailed specifications of weight 1112 are as follows: Outer diameter c:50.0mm Diameter of center hole 1130 d: 16.0 mm Height e: 39.0 mm
[0184] The detailed specifications of the piston head 1118 are as follows: Diameter f: 59.7mm (±0.05mm) Height g: 16.5mm. The height of the piston head must not be less than 15.0mm. Outer holes 1214 (14 total) have a diameter h of 9.30 (±0.25) mm, the outer holes 1214 are evenly spaced and the centers are 23.9 mm from the center of the central hole 1218. Inner holes 1216 (7 total) having diameter i of 9.30 (±0.25) mm, inner holes 1216 are evenly spaced and centers are 13.4 mm from the center of central hole 1218. The central bore 1218 has a diameter j of approximately 5 / 8 inch (15.9 mm) and is threaded to receive the lower portion 1146 of the piston shaft 1114 .
[0185] Prior to use, the stainless steel screens (not shown) in the piston head 1118 and cylinder 1120 should be inspected for clogging, holes, or overstretching and replaced if necessary. A urine permeability meter with a damaged screen may give erroneous UPM results and should not be used until the screens are replaced.
[0186] A 5.00 cm mark 1156 is scribed on the cylinder 1120 at a height k of 5.00 cm (±0.05 cm) above a screen (not shown) attached to the bottom 1148 of the cylinder 1120. This marks the fluid level to be maintained during the analysis. Maintaining an accurate and consistent fluid level (hydrostatic pressure) is important for measurement accuracy.
[0187] The constant hydrostatic head reservoir 1014 is used to supply the cylinder 1120 with saline solution 1032 and maintain the level of the saline solution 1032 at a height k of 5.00 cm above a screen (not shown) attached to the bottom 1148 of the cylinder 1120. The bottom 1034 of the air intake tube 1010 is positioned to maintain the level of the saline solution 1032 in the cylinder 1120 at the height k of 5.00 cm required during measurement, i.e., the bottom 1034 of the air tube 1010 is on approximately the same plane 1038 as the 5.00 cm mark 1156 on the cylinder 1120 when placed above the receiving vessel 1024 and on the cover plate 1047 and support ring 1040 (the inner opening of the circle is 64 mm or greater in diameter).
[0188] The cover plate 1047 and the support ring 1040 are parts used in an instrument used for the method "K(t) Test Method (Dynamic Effective Permeability and Uptake Rate Measurement Test Method)" as described, for example, in WO 2021 / 188330, called "Zeitabhangiger Durchlassigkeitsprufstand" or "Time Dependent Permeability Tester", instrument number 03-080578, and available from BRAUN GmbH, Frankfurter Str. 145, 61476 Kronberg, Germany. Detailed drawings are also available on request.
[0189] Proper height alignment of the intake tube 1010 and the 5.00 cm mark 1156 on the cylinder 1120 is important for the analysis. The preferred reservoir 1014 consists of a jar 1030 containing a horizontally oriented L-shaped conduit 1018 connected to a flexible tube 1045 (e.g., Tygon tubing through which a nozzle and reservoir outlet can be connected) and a Tygon tube nozzle 1044 (inner diameter at least 6.0 mm, length approximately 5.0 cm) for fluid delivery, a vertically oriented open-ended tube 1010 for admitting air at a fixed height within the constant hydrostatic head reservoir 1014, and a stoppered vent 1012 for refilling the constant hydrostatic head reservoir 1014. The tube 1010 has an inner diameter of approximately 12 mm, but not less than 10.5 mm. A conduit 1018 positioned near the bottom 1042 of the constant hydrostatic head reservoir 1014 includes a stopcock 1020 for starting / stopping the delivery of saline solution 1032. An outlet 1044 of a delivery flexible tube 1045 is sized (e.g., 10 mm outer diameter) to be inserted through a second lid opening 1136 of the cylinder lid 1116, with its end positioned below the surface of the saline solution 1032 in the cylinder 1120 (after a 5.00 cm height of saline solution 1032 has been obtained in the cylinder 1120). The intake tube 1010 is held in place with an O-ring collar 1049. The constant hydrostatic head reservoir 1014 may be positioned on a laboratory reck 1016 at a suitable height relative to the height of the cylinder 1120. The components of the constant hydrostatic head reservoir 1014 are sized to rapidly fill the cylinder 1120 to the required height (i.e., hydrostatic head) and maintain this height for the duration of the measurement. The constant hydrostatic head reservoir 1014 must be capable of delivering saline solution 1032 at a flow rate of at least 2.6 g / sec for at least 10 minutes.
[0190] The piston / cylinder assembly 1028 is positioned on a support ring 1040 in a cover plate 1047 or suitable alternative rigid stand. Saline solution 1032 passing through the piston / cylinder assembly 1028 containing the swollen hydrogel layer 1318 is collected in a receiving vessel 1024 positioned below (but not in contact with) the piston / cylinder assembly 1028.
[0191] The receiving vessel 1024 is positioned on a balance 1026 having an accuracy of at least 0.001 g. The digital output of the balance 1026 is coupled to a computerized data acquisition system 1048.
[0192] Preparation of reagents (not shown) Jayco Synthetic Urine (JSU) 1312 is used for the swelling phase (see UPM procedure below) and 0.118 M Sodium Chloride (NaCl) solution 1032 is used for the flow phase (see UPM procedure below). The following preparations are for a standard 1 liter volume. For preparations of volumes other than 1 liter, all amounts are scaled accordingly.
[0193] JSU: Fill a 1 L volumetric flask with distilled water to 80% of its volume and place a magnetic stir bar in the flask. Using separate weighing paper or a beaker, weigh out the following amounts of dry ingredients to within ±0.01 g using an analytical balance and quantitatively add to the volumetric flask in the same order as listed below. The solution is stirred on a suitable stir plate until all solids have melted, the stir bar is removed and the solution is diluted to 1 L volume with distilled water. The stir bar is reinserted and the solution is stirred on the stir plate for an additional few minutes.
[0194] How much salt to make 1 liter of Jayco synthetic urine? Potassium chloride (KCl) 2.00g Sodium sulfate (Na2SO4) 2.00g Ammonium dihydrogen phosphate (NH4H2PO4) 0.85g Ammonium phosphate, dibasic ((NH4)2HPO4) 0.15 g Calcium chloride (CaCl2) 0.19 g - [or calcium chloride hydrate (CaCl2·2H2O) 0.25 g] Magnesium chloride (MgCl2) 0.23 g - [or magnesium chloride hydrate (MgCl2·6H2O) 0.50 g]
[0195] For a faster preparation, potassium chloride, sodium sulfate, ammonium dihydrogen phosphate, ammonium phosphate (dibasic), and magnesium chloride (or magnesium chloride hydrate) are combined and dissolved in 80% distilled water in a 1 L volumetric flask. Calcium chloride (or calcium chloride hydrate) is dissolved separately (e.g., in a glass beaker) in about 50 mL of distilled water, and after the other salts have completely dissolved, the calcium chloride solution is transferred to the 1 L volumetric flask. Distilled water is then added to 1 L (1000 mL ± 0.4 mL) and the solution is stirred for a few more minutes. Jayco synthetic urine can be stored in a clean plastic container for 10 days. If the solution becomes cloudy, it should not be used.
[0196] 0.118M Sodium Chloride (NaCl) Solution: 0.118M sodium chloride is used as Saline 1032. Using weighing paper or a beaker, weigh out 6.90 g (± 0.01 g) of sodium chloride and quantitatively transfer to a 1 L volumetric flask (1000 mL ± 0.4 mL) and fill the flask to volume with distilled water. Add a stir bar and mix the solution on a stir plate until all solids are dissolved.
[0197] The conductivity of the prepared Jayco solution should be in the range of about 7.48-7.72 mS / cm, and the conductivity of the prepared 0.118M sodium chloride (NaCl) solution should be in the range of about 12.34-12.66 mS / cm (e.g., measured via a COND 70 INSTRUMENT without cell #50010522 equipped with Cell VPT51-01 C=0.1 from xs instruments, or via an LF320 / set #300243 equipped with TetraCon325 from WTW, or a COND330i equipped with TetraCon325, #02420059 from WTW). The surface tension of each solution should be in the range of 71-75 mN / m (e.g., measured via a surface tensiometer K100 equipped with Pt plate from Kruess).
[0198] Exam Preparation A solid reference cylinder weight (not shown) (diameter 50 mm; height 128 mm) is used to set a caliper gauge (not shown) (25 mm measurement range, 0.01 mm accuracy, 50 g maximum piston pressure; e.g., Mitutoyo Digimatic Height Gage) to a reading of 0. This is conveniently performed on a smooth, level bench (not shown) that is at least about 11.5 cm by 15 cm. The piston / cylinder assembly 1028, which does not contain superabsorbent polymer particles, is positioned under the caliper gauge (not shown) and the reading L1 is recorded to the nearest 0.01 mm.
[0199] The constant hydrostatic head reservoir 1014 is filled with saline solution 1032. The bottom 1034 of the intake tube 1010 is positioned to maintain the top (not shown) of the liquid meniscus (not shown) in the cylinder 1120 at the 5.00 cm mark 1156 during measurement. Proper height alignment of the intake tube 1010 on the cylinder 1120 at the 5.00 cm mark 1156 is important to the analysis.
[0200] The receiving vessel 1024 is placed on a balance 1026, the digital output of which is connected to a computerized data acquisition system 1048. A cover plate 1047 with a support ring 1040 is positioned above the receiving vessel 1024.
[0201] UPM Procedure Using an analytical balance, weigh 1.5g (±0.05g) of superabsorbent polymer particles onto a suitable weighing paper or weighing aid. The moisture content of the superabsorbent polymer particles is measured according to EDANA moisture content test method NWSP 230.0.R2(15) or via a moisture analyzer (HX204 from Mettler Toledo, drying temperature 130°C, starting superabsorbent weight 3.0g (±0.5g), stop criterion 1mg / 140sec). If the moisture content of the superabsorbent polymer particles is greater than 3% by weight, dry the superabsorbent polymer particles, for example, in an oven at 105°C for 3 hours, or for example, in an oven at 120°C for 2 hours, until the moisture level is <3% by weight.
[0202] The empty cylinder 1120 is placed on a horizontal bench top (not shown) and the superabsorbent polymer particles are quantitatively transferred into the cylinder 1120. The superabsorbent polymer particles are evenly distributed on a screen (not shown) attached to the bottom 1148 of the cylinder 1120 while rotating the cylinder 1120, for example with the assistance of a (manual or motorized) turntable (e.g., petriturn-E or petriturn-M made by Schuett). For the most precise results, it is important to distribute the particles evenly on the screen (not shown) attached to the bottom 1148 of the cylinder 1120. After the superabsorbent polymer particles are evenly distributed on the screen (not shown) attached to the bottom 1148 of the cylinder 1120, the particles should not stick to the inner cylinder wall 1150. The piston shaft 1114 is inserted through the first lid opening 1134 with the lip 1154 of the lid 1116 facing the piston head 1118. The piston head 1118 is carefully inserted into the cylinder 1120 to a depth of several centimeters. The lid 1116 is then placed on the upper rim 1144 of the cylinder 1120, taking care to keep the piston head 1118 away from the superabsorbent polymer particles. The weight 1112 is positioned on the top 1128 of the piston shaft 1114 so that it rests on the shoulder 1124, thereby aligning the first and second linear indicator marks. The lid 1116 and piston shaft 1126 are then carefully rotated so that the third, fourth, fifth, and sixth linear indicator marks are aligned with the first and second linear indicator marks. The piston head 1118 is then gently pressed down (via the piston shaft 1114) onto the dried superabsorbent polymer particles. Proper placement of the lid 1116 prevents binding of the weight and ensures an even distribution of the weight on the hydrogel layer 1318.
[0203] Swelling phase: A fritted disk 1310 having a diameter of at least 8 cm (e.g., 8-9 cm diameter) and a thickness of at least 5.0 mm (e.g., 5-7 mm thickness) and having "coarse" or "very coarse" porosity (e.g., Chemglass Inc. #CG 201-51, coarse porosity; or e.g., Robu 1680, with zero porosity) is placed in a flat-bottomed Petri dish 1314 and JSU 1312 is added by pouring it into the center of the fritted disk 1310 until it reaches the top surface 1316 of the fritted disk 1310. The height of the JSU should not exceed the height of the fritted disk 1310. It is important to avoid any air or bubbles being trapped in or under the fritted disk 1310.
[0204] The entire piston / cylinder assembly 1028 is lifted and placed on the fritted disk 1310 in the Petri dish 1314. The JSU 1312 from the Petri dish 1314 passes through the fritted disk 1310 and is absorbed by the superabsorbent polymer particles (not shown) to form the hydrogel layer 1318. The JSU 1312 available in the Petri dish 1314 should be sufficient for all of the swelling phase. If necessary, more JSU 1312 may be added to the Petri dish 1314 during the hydration period to maintain a liquid level of JSU 1312 on the top surface 1316 of the fritted disk 1310. After the 60 minute period, the piston / cylinder assembly 1028 is removed from the fritted disk 1310, taking care that the hydrogel layer 1318 does not lose JSU 1312 or entrap air during this procedure. The piston / cylinder assembly 1028 is placed under a caliper gauge (not shown) and the reading L2 is recorded to the nearest 0.01 mm. If the reading changes over time, only the initial value is recorded. The thickness L0 of the hydrogel layer 1318 is determined from L2 - L1 to the nearest 0.1 mm.
[0205] The piston / cylinder assembly 1028 is transferred to the support ring 1040 in the cover plate 1047. The constant hydrostatic head reservoir 1014 is positioned so that the conduit nozzle 1044 is located through the second lid opening 1136. The measurement is initiated in the following sequence: a) The stopcock 1020 of the constant hydrostatic head reservoir 1014 is opened allowing the saline solution 1032 to reach the 5.00 cm mark 1156 on the cylinder 1120. This saline solution 1032 level should be achieved within 10 seconds of opening the stopcock 1020. b) Once 5.00 cm of saline 1032 is achieved, begin the data collection program.
[0206] A computer 1048 attached to the balance 1026 is used to record the amount of saline 1032 (in grams, with an accuracy of 0.001 grams) passing through the hydrogel layer 1318 at 20 second intervals for 10 minutes. At the end of the 10 minute period, the stopcock 1020 on the constant hydrostatic head reservoir 1014 is closed.
[0207] Data from 60 seconds to the end of the experiment are used for the UPM calculation. Data collected prior to 60 seconds are not included in the calculation.
[0208] After the first 60 seconds of the experiment, each 20-second period (time t (i-1) ~t i ) for each flow velocity Fs (t) (unit: g / s) and time t (1 / 2)t Calculate the midpoint of each (in seconds) according to the following formula:
[0209]
number
[0210] At each time interval (t (i-1) ~t i ) flow velocity Fs (t) is the time interval (t (i-1) ~t i ) time t (1 / 2)t The intercept is calculated as Fs(t=0).
[0211] Calculate the intercept: The intercept is calculated via the best fit regression line, for example as follows: The equation for the intercept of the regression line a is:
[0212]
number
[0213]
number
[0214] Calculation of urine permeability measurement Q: The intercept Fs(t=0) is used to calculate Q according to the following formula:
[0215]
number
[0216] [Table 6]
[0217] SAP K(t) test method This method determines the time-dependent effective permeability SAP K(t) and uptake rate of a gel layer formed from hydrogel-forming superabsorbent polymer particles or in an absorbent structure containing such particles under confining pressure. The purpose of this method is to evaluate the ability of a gel layer formed from hydrogel-forming superabsorbent polymer particles or an absorbent structure containing them to acquire and distribute body fluids when the polymers are present in high concentrations in the absorbent article and are subjected to mechanical pressures such as those typically encountered during use of the absorbent article. The effective permeability is calculated using Darcy's law and the steady flow method (see below). See also, for example, "Absorbency," ed. By PK Chatterjee, Elsevier, 1982, Pages 42-43, and "Chemical Engineering Vol. II, Third Edition, JM Coulson and JF Richardson, Pergamon Press, 1978, Pages 122-127.
[0218] Unlike previously published methods, the samples are not pre-swollen and therefore no hydrogel is formed by pre-swelling hydrogel-forming superabsorbent polymer particles in synthetic urine, but the measurement starts with a dry structure. The instrument used for this method is called "Zeitabhangiger Durchlassigkeitsprufstand" or "Time Dependent Permeability Tester" (instrument number 03-080578), is commercially available from BRAUN GmbH (Frankfurter Str. 145, 61476 Kronberg, Germany) and is described below. Operating instructions, wiring diagrams, and detailed technical drawings are also available upon reasonable request.
[0219] A detailed description of the instrument (Dynamic Effective Permeability and Uptake Rate Measurement System) and its handling is further disclosed in WO 2015 / 041784 A1 (Peri et al., P&G).
[0220] According to the required precision known to one of skill in the art, the average values of T20, T80%, K20, U20, and Kmin / K20 from the three replicates are recorded.
[0221] others As used herein, the terms "comprise(s)" and "comprising" are open-ended, each specifying the presence of the subsequently described feature, e.g., component, but not excluding the presence of other features, e.g., elements, steps, or components known in the art or disclosed herein. These terms based on the verb "comprise" should be interpreted to encompass the narrower term "consisting essentially of," which excludes any unmentioned element, step, or ingredient that significantly affects the way in which the feature performs its function, and the term "consisting of," which excludes any unspecified element, step, or ingredient. Any preferred or exemplary embodiments described below do not limit the scope of the claims unless specifically indicated otherwise. Words such as "typically," "usually," "preferably," "advantageously," and "specifically" also modify features that are not intended to limit the scope of the claims, unless specifically indicated to do so. Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0222] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or benefit, are incorporated herein by reference in their entirety, unless expressly stated to the contrary. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest, or disclose any such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition given to that term in this document shall govern.
[0223] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.
Claims
1. An absorbent article (20), comprising: - a liquid-permeable topsheet (24); an absorbent core (28) comprising an upper core wrap layer (45), a lower core wrap layer (46), and a layer of superabsorbent polymer particles (60) disposed between said upper and lower core wrap layers; an upper acquisition and distribution system (52, 54), said upper acquisition and distribution system consisting of one or more layers disposed between said topsheet and said absorbent core, said upper acquisition and distribution system being substantially free of unbonded crosslinked cellulosic fibers; a liquid-impermeable backsheet (25), The superabsorbent polymer particles have a viscosity of at least 45.10, as measured by the UPM method described herein. -7 (cm 3 - The absorbent article (20) having a urine permeability measurement (UPM) of 0.01g / g.
2. The superabsorbent polymer particles are 55.10 -7 ~90.10 -7 (cm 3 2. The absorbent article of claim 1, having a UPM in the range of s / g.
3. 3. The absorbent article of claim 1 or 2, wherein the superabsorbent polymer particles have an effective capacity (EFFC) of greater than 23 g / g, the effective capacity being measured as described herein.
4. The absorbent article of claim 3, wherein said superabsorbent polymer particles have an EFFC in the range of 23.5 g / g to 29 g / g.
5. The absorbent article according to any one of claims 1 to 4, wherein said superabsorbent polymer particles are not mixed with cellulose fibres.
6. The absorbent article of any one of claims 1 to 5, wherein the upper acquisition and distribution system comprises at least one spunlace layer.
7. The absorbent article of any one of claims 1 to 6, wherein the upper acquisition and distribution system comprises a first layer and a second layer, the first layer being closer to the topsheet and the second layer being closer to the absorbent core, the first layer being a nonwoven acquisition layer (52) and the second layer being a nonwoven distribution layer (54).
8. The absorbent article of claim 7, wherein said second layer (54) is a spunlace nonwoven.
9. 9. The absorbent article according to any one of claims 1 to 8, further comprising a lower acquisition and distribution layer (56) between the layer of superabsorbent polymer particles and the backsheet, said lower acquisition and distribution layer comprising or consisting of a nonwoven layer, in particular a carded nonwoven layer.
10. The absorbent article of claim 9, wherein said lower acquisition and distribution layer has a basis weight of from 20 gsm to 100 gsm, preferably from 30 gsm to 50 gsm.
11. The absorbent article of claim 9 or 10, wherein said lower acquisition and distribution layer (56) comprises a surfactant coating and / or a hydrophilic melt additive.
12. The absorbent article of any one of claims 8 to 11, wherein the lower acquisition and distribution layer (56) is disposed between the lower core wrap layer (46) and the backsheet (25), and the lower acquisition and distribution layer (56) and the lower core wrap layer (46) are both hydrophilic, but the lower acquisition and distribution layer (56) is less hydrophilic than the lower core wrap layer (46).
13. 13. The absorbent article of any one of claims 1 to 12, wherein at least some of the superabsorbent polymer particles are secured by a thermoplastic fiber net on at least one of the upper core wrap layer (45) or the lower core wrap layer (46).
14. The absorbent article according to any one of the preceding claims, wherein said layer (60) of superabsorbent polymer particles comprises at least one longitudinally extending channel (26) which does not contain superabsorbent polymer particles.
15. The absorbent article according to any one of claims 1 to 14, wherein said superabsorbent polymer particles are obtained by surface crosslinking of a precursor SAP, said precursor SAP being preferably internally crosslinked.
Citation Information
Patent Citations
Absorbent article, and absorbent core that forms channels when wet
JP2016523137A
Predicting the physical properties of superabsorbent polymers
JP2022509222A
Absorbent article comprising a lower acquisition and distribution system
US20210177672A1
Disposable Absorbent Article With Improved Acquisition System
US20080312622A1
Absorbent articles
US20210106471A1